Biodegradable plastic derived from shrimp shell waste and method of preparation thereof

KR103007372B1Active Publication Date: 2026-09-01ZERO ONE PARTNERS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020250046099
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2026-09-01
Estimated Expiration
2045-04-09

Smart Images

  • Figure 1020250046099
    Figure 1020250046099
Patent Text Reader

Abstract

The present invention relates to a biodegradable plastic utilizing shrimp shell byproducts and a method for manufacturing the same, comprising the steps of: collecting shrimp shell byproducts and washing them in a purified form; extracting chitin from the washed shrimp shell byproducts; deacetylating the extracted chitin to produce chitosan; mixing a plasticizer, a filler, and a biodegradable auxiliary polymer with the chitosan; and molding the mixture to produce a biodegradable plastic product. Specifically, high-quality chitosan is produced by introducing ultrasonic technology into the pretreatment process of shrimp shells, utilizing enzymatic methods in the chitin extraction process, and employing microwave-assisted deacetylation technology and the addition of antioxidants. Furthermore, chitosan nanocomposites with enhanced mechanical properties and thermal stability are formed through biological crosslinking using the natural crosslinking agent zennipin and the addition of graphene oxide nanofillers, and plastics with controlled flexibility and biodegradability are manufactured by adding vegetable oil-based plasticizers and biodegradable auxiliary polymer blends. The biodegradable plastic produced according to the present invention has the characteristics of having a tensile strength improved by more than 30%, an elongation rate increased by more than 50%, and biodegradation of more than 90% within 180 days, so it can be utilized in the development of environmentally friendly plastic products.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a biodegradable plastic utilizing shrimp shell byproducts, which are fisheries waste, and a method for manufacturing the same. More specifically, the invention relates to a method for manufacturing an eco-friendly plastic with excellent mechanical properties and a controlled biodegradation rate by extracting chitin from shrimp shells, deacetylating it to convert it into chitosan, and then mixing it with a plasticizer, a filler, and a biodegradable auxiliary polymer. The present invention relates to the field of developing eco-friendly materials capable of increasing the recycling rate of marine and fisheries waste and reducing environmental pollution caused by plastic waste. Background Technology

[0002] Petroleum-based plastics are widely used due to their excellent properties, such as lightweightness, durability, processability, and cost-effectiveness; however, they cause serious environmental pollution because they do not decompose in the natural environment. Consequently, the development of eco-friendly biodegradable plastics is actively underway, and interest is particularly growing in biodegradable plastics utilizing renewable biological resources.

[0003] Shrimp shells contain a large amount of a natural polymer called chitin, giving them high potential as a raw material for biodegradable plastics. Chitin is the second most abundant biopolymer in nature after cellulose and can be converted into chitosan through deacetylation. Chitosan is attracting attention in various application fields due to its properties such as biocompatibility, biodegradability, non-toxicity, and antimicrobial activity.

[0004] Conventional methods for manufacturing chitosan-based biodegradable plastics generally involve the use of high concentrations of acids and alkalis during the extraction and deacetylation processes of chitin, resulting in a heavy environmental burden. Additionally, they require processing for a long time under harsh conditions of high temperature and pressure, leading to high energy consumption. Furthermore, the manufactured chitosan-based plastics have low mechanical properties, are susceptible to moisture, and lack thermal stability, which has limited their practical application.

[0005] Therefore, there is a need to develop an eco-friendly and economical manufacturing method capable of efficiently extracting chitin from shrimp shell byproducts and converting it into chitosan to produce biodegradable plastics with excellent physical properties. Prior art literature

[0006] Korean Registered Patent 10-1344471 Korean Registered Patent 10-2754680 Korean Published Patent 10-2199848 Korean Published Patent 10-1035727 The problem to be solved

[0007] The present invention was devised to solve the above-mentioned problems and aims to provide a method for manufacturing a biodegradable plastic with improved mechanical properties, thermal stability, and moisture resistance by efficiently extracting chitin from shrimp shell byproducts, deacetylating it to produce chitosan, and then mixing it with a crosslinking agent, a nano-filler, and a biodegradable auxiliary polymer.

[0008] Specifically, the present invention aims to solve the following problems:

[0009] First, we aim to provide a method to increase purification efficiency and reduce processing time by introducing ultrasonic technology into the pretreatment process of shrimp shell by-products.

[0010] Second, by introducing an enzymatic method in the chitin extraction process, we aim to reduce the use of harmful chemicals in the chemical treatment process and provide an environmentally friendly extraction method.

[0011] Third, we aim to provide a method that improves the deacetylation efficiency of chitin and shortens the processing time by introducing microwave-assisted deacetylation technology, and inhibits the reduction of the molecular weight of chitosan by adding an antioxidant.

[0012] Fourth, we aim to provide a method for manufacturing a chitosan nanocomposite with improved mechanical properties and thermal stability by crosslinking chitosan using zennipin, a natural crosslinking agent, and adding graphene oxide as a nanofiller.

[0013] Fifth, we aim to provide a method for manufacturing a biodegradable plastic with a controlled biodegradation rate by adding epoxidized soybean oil, a vegetable oil-based plasticizer, to impart flexibility, and adding a biodegradable auxiliary polymer blend of starch and polycaprolactone. means of solving the problem

[0014] The present invention provides a method for manufacturing a biodegradable plastic utilizing shrimp shell by-products, comprising: (a) collecting shrimp shell by-products and washing them in a purified form; (b) extracting chitin from the washed shrimp shell by-products; (c) deacetylating the extracted chitin to produce chitosan; (d) mixing a plasticizer, a filler, and a biodegradable auxiliary polymer with the chitosan; and (e) molding the mixture to produce a biodegradable plastic product.

[0015] At this time, the above step (a) comprises: (a1) immersing the collected shrimp shell by-products in an aqueous solution in which 0.5-1.5 parts by weight of sodium chloride are dissolved in 100 parts by weight of water to remove foreign substances; (a2) treating the immersed shrimp shell by-products for 15-25 minutes using an ultrasonic cleaner having a frequency of 20-40 kHz at a temperature of 45-55°C; (a3) ​​treating the ultrasonically treated shrimp shell by-products for 2-3 hours at 60-70°C with an aqueous solution in which 0.8-1.2 parts by weight of sodium hydroxide are dissolved in 100 parts by weight of water to remove water-soluble proteins; (a4) washing the protein-removed shrimp shell by-products with deionized water until the pH reaches 6.8-7.2 when measured with a pH meter to neutralize them. and (a5) a step of vacuum drying the neutralized shrimp shell byproduct at 60-70°C for 8-12 hours so that the moisture content is 5% or less when measured by weight;

[0016] At this time, the above step (b) comprises: (b1) a step of demineralizing the washed shrimp shell by-product for 4-6 hours at room temperature using a solution obtained by diluting 1.8-2.2 parts by weight of hydrochloric acid with 100 parts by weight of water to remove minerals contained in the by-product; (b2) a step of extracting the demineralized shrimp shell by-product with a mixed solvent of ethanol and acetone (volume ratio 3:2) at 40-50°C for 3-4 hours to remove pigments; (b3) a step of adding 2-5 parts by weight of an enzyme complex containing commercially available Alcalase® protease and Novozym® lipase in a 1:1 weight ratio to 100 parts by weight of the shrimp shell by-product to the pigment-removed shrimp shell by-product, and performing enzymatic extraction for 12-18 hours under conditions of 38-42°C and pH 5.8-6.2; (b4) centrifuging the enzymatic extract (5000-6000 rpm, (b5) a step of obtaining a chitin precipitate by washing the chitin precipitate three times with distilled water and then drying it under reduced pressure at 45-55°C for 10-14 hours using a porous silica drying agent to obtain chitin with a purity of 92% or higher when measured by FTIR analysis;

[0017] At this time, the above step (c) comprises: (c1) dispersing the extracted chitin in a solution in which 35-45 parts by weight of sodium hydroxide is dissolved in 100 parts by weight of water for microwave-assisted deacetylation, such that the ratio of chitin to the solution is 1:10 (w / v); (c2) adding 0.5-1.5 parts by weight of ascorbic acid, an antioxidant, to the chitin dispersion per 100 parts by weight of chitin to inhibit the decrease in molecular weight of chitosan during the deacetylation process; (c3) treating the mixture in a microwave reactor at a frequency of 2.45 GHz and an output of 600-800 W for a total of 6-8 cycles, with irradiation followed by a 2-minute rest as one cycle; (c4) washing the microwave-treated mixture at least 5 times with distilled water until the pH reaches 7.0-7.5 when measured with a pH meter to neutralize it; (c5) the neutralized chitosan The method comprises the steps of: (c6) dissolving 0.8-1.2 parts by weight of acetic acid in a solution of 100 parts by weight of water, and then filtering using a 0.45 μm filter to remove insoluble substances; and (c6) freeze-drying the filtered chitosan solution to obtain high-quality chitosan powder having a degree of deacetylation of 85% or more as measured by H-NMR analysis and a molecular weight of 150-250 kDa as measured by GPC (gel permeation chromatography).

[0018] At this time, the above step (d) comprises: (d1) a step of preparing crosslinked chitosan with improved thermal stability by reacting the chitosan with 0.5-1.5 parts by weight of genipin, a natural crosslinking agent, per 100 parts by weight of chitosan for biological crosslinking at 70-80°C for 2-4 hours; (d2) a step of forming a nanocomposite with a tensile strength improved by 30% or more by adding 0.3-0.7 parts by weight of graphene oxide per 100 parts by weight of the crosslinked chitosan and ultrasonically treating at a frequency of 20-30 kHz for 15-25 minutes; (d3) a step of imparting flexibility with an elongation improved by 50% or more when measured by the ASTM D638 test method by adding 15-25 parts by weight of epoxidized soybean oil, a vegetable oil-based plasticizer, per 100 parts by weight of the nanocomposite; (d4) per 100 parts by weight of the mixture, starch and The method is characterized by comprising: a step of forming a composition that is 90% or more biodegradable within 180 days when measured by ASTM D5338 test method by adding 30-40 parts by weight of a biodegradable auxiliary polymer blend mixed with polycaprolactone (PCL) in a 1:2 weight ratio; and (d5) a step of melt-mixing the mixture using a twin-screw extruder under conditions of 160-180℃ and 50-60rpm, extruding it into a pellet shape with a diameter of 3-5mm, and then drying it at 50-60℃ for 12-18 hours to produce a biodegradable plastic pellet having a moisture content of 1% or less when measured by weight. Effects of the invention

[0019] The biodegradable plastic utilizing shrimp shell by-products and the method for manufacturing the same according to the present invention have the following effects:

[0020] First, converting shrimp shell byproducts, which are fisheries waste, into high-value-added materials has economic effects such as reducing waste disposal costs and improving resource recycling rates.

[0021] Second, by introducing ultrasonic technology and enzymatic methods to extract chitin from shrimp shells, it has an environmental effect of reducing the environmental burden by decreasing the use of chemicals and lowering energy consumption.

[0022] Third, the microwave-assisted deacetylation technology reduces processing time and increases energy efficiency, and the addition of antioxidants enables the production of high molecular weight chitosan, thereby contributing to the improvement of the physical properties of the final product.

[0023] Fourth, the chitosan nanocomposite prepared through biological crosslinking using gennipin and the addition of graphene oxide nanofillers has the effect of exhibiting excellent physical properties, such as tensile strength improved by more than 30% and thermal stability improved compared to existing chitosan-based plastics.

[0024] Fifth, the addition of epoxidized soybean oil, a vegetable oil-based plasticizer, has the effect of providing an eco-friendly plastic material that has flexibility with an elongation rate improved by more than 50%, and the addition of a starch and polycaprolactone blend has the effect of biodegrading by more than 90% within 180 days.

[0025] Sixth, the biodegradable plastic produced according to the present invention is an eco-friendly material that can replace existing petroleum-based plastics, and can be applied in various fields such as disposable products, food packaging materials, agricultural films, and medical materials, and can contribute to reducing environmental pollution caused by plastic waste. Specific details for implementing the invention

[0026] Hereinafter, embodiments are described in detail with reference to the attached drawings. However, various modifications may be made to the embodiments, and thus the scope of the patent application is not limited or restricted by these embodiments. It should be understood that all modifications, equivalents, and substitutions to the embodiments are included within the scope of the rights.

[0027] Specific structural or functional descriptions of the embodiments are disclosed for illustrative purposes only and may be modified and implemented in various forms. Accordingly, the embodiments are not limited to the specific disclosed forms, and the scope of this specification includes modifications, equivalents, or substitutions that fall within the technical concept.

[0028] Terms such as "first" or "second" may be used to describe various components, but these terms should be interpreted solely for the purpose of distinguishing one component from another. For example, the first component may be named the second component, and similarly, the second component may be named the first component.

[0029] When it is stated that a component is "connected" to another component, it should be understood that it may be directly connected to or coupled with that other component, or that there may be other components in between.

[0030] The terms used in the embodiments are for illustrative purposes only and should not be interpreted as intended to be limiting. Singular expressions include plural expressions unless the context clearly indicates otherwise. In this specification, terms such as "comprising" or "having" are intended to indicate the existence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.

[0031] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the embodiments pertain. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this application.

[0032] The advantages and features of the present invention and the methods for achieving them will become clear by referring to the embodiments described below in detail together with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below but may be implemented in various different forms. These embodiments are provided merely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the scope of the invention, and the present invention is defined only by the scope of the claims.

[0033] In the embodiments of the present invention, unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in the embodiments of the present invention.

[0034] The shapes, sizes, ratios, angles, numbers, etc. disclosed in the drawings for explaining embodiments of the present invention are exemplary, and therefore the present invention is not limited to the depicted details. Furthermore, in describing the present invention, if it is determined that a detailed description of related known technology may unnecessarily obscure the essence of the present invention, such detailed description is omitted. Where terms such as "includes," "has," or "is made up" are used in this specification, other parts may be added unless "only" is used. Where a component is expressed in the singular, it includes cases where it includes the plural unless specifically stated otherwise.

[0035] In interpreting the components, they are interpreted to include a margin of error even in the absence of a separate explicit statement.

[0036] The size and thickness of each component shown in the drawings are illustrated for convenience of explanation, and the present invention is not necessarily limited to the size and thickness of the illustrated components.

[0037] The features of each of the various embodiments of the present invention may be combined or combined with one another, either partially or wholly, and as will be fully understood by those skilled in the art, various technical interlocking and operation are possible, and each embodiment may be implemented independently of one another or together in an interlocking relationship.

[0038] The present invention provides a method for manufacturing a biodegradable plastic utilizing shrimp shell by-products, comprising: (a) collecting shrimp shell by-products and washing them in a purified form; (b) extracting chitin from the washed shrimp shell by-products; (c) deacetylating the extracted chitin to produce chitosan; (d) mixing a plasticizer, a filler, and a biodegradable auxiliary polymer with the chitosan; and (e) molding the mixture to produce a biodegradable plastic product.

[0039] At this time, the above step (a) comprises: (a1) immersing the collected shrimp shell by-products in an aqueous solution in which 0.5-1.5 parts by weight of sodium chloride are dissolved in 100 parts by weight of water to remove foreign substances; (a2) treating the immersed shrimp shell by-products for 15-25 minutes using an ultrasonic cleaner having a frequency of 20-40 kHz at a temperature of 45-55°C; (a3) ​​treating the ultrasonically treated shrimp shell by-products for 2-3 hours at 60-70°C with an aqueous solution in which 0.8-1.2 parts by weight of sodium hydroxide are dissolved in 100 parts by weight of water to remove water-soluble proteins; (a4) washing the protein-removed shrimp shell by-products with deionized water until the pH reaches 6.8-7.2 when measured with a pH meter to neutralize them. and (a5) a step of vacuum drying the neutralized shrimp shell byproduct at 60-70°C for 8-12 hours so that the moisture content is 5% or less when measured by weight;

[0040] At this time, the above step (b) comprises: (b1) a step of demineralizing the washed shrimp shell by-product for 4-6 hours at room temperature using a solution obtained by diluting 1.8-2.2 parts by weight of hydrochloric acid with 100 parts by weight of water to remove minerals contained in the by-product; (b2) a step of extracting the demineralized shrimp shell by-product with a mixed solvent of ethanol and acetone (volume ratio 3:2) at 40-50°C for 3-4 hours to remove pigments; (b3) a step of adding 2-5 parts by weight of an enzyme complex containing commercially available Alcalase® protease and Novozym® lipase in a 1:1 weight ratio to 100 parts by weight of the shrimp shell by-product to the pigment-removed shrimp shell by-product, and performing enzymatic extraction for 12-18 hours under conditions of 38-42°C and pH 5.8-6.2; (b4) centrifuging the enzymatic extract (5000-6000 rpm, (b5) a step of obtaining a chitin precipitate by washing the chitin precipitate three times with distilled water and then drying it under reduced pressure at 45-55°C for 10-14 hours using a porous silica drying agent to obtain chitin with a purity of 92% or higher when measured by FTIR analysis;

[0041] At this time, the above step (c) comprises: (c1) dispersing the extracted chitin in a solution in which 35-45 parts by weight of sodium hydroxide is dissolved in 100 parts by weight of water for microwave-assisted deacetylation, such that the ratio of chitin to the solution is 1:10 (w / v); (c2) adding 0.5-1.5 parts by weight of ascorbic acid, an antioxidant, to the chitin dispersion per 100 parts by weight of chitin to inhibit the decrease in molecular weight of chitosan during the deacetylation process; (c3) treating the mixture in a microwave reactor at a frequency of 2.45 GHz and an output of 600-800 W for a total of 6-8 cycles, with irradiation followed by a 2-minute rest as one cycle; (c4) washing the microwave-treated mixture at least 5 times with distilled water until the pH reaches 7.0-7.5 when measured with a pH meter to neutralize it; (c5) the neutralized chitosan The method comprises the steps of: (c6) dissolving 0.8-1.2 parts by weight of acetic acid in a solution of 100 parts by weight of water, and then filtering using a 0.45 μm filter to remove insoluble substances; and (c6) freeze-drying the filtered chitosan solution to obtain high-quality chitosan powder having a degree of deacetylation of 85% or more as measured by H-NMR analysis and a molecular weight of 150-250 kDa as measured by GPC (gel permeation chromatography).

[0042] At this time, the above step (d) comprises: (d1) a step of preparing crosslinked chitosan with improved thermal stability by reacting the chitosan with 0.5-1.5 parts by weight of genipin, a natural crosslinking agent, per 100 parts by weight of chitosan for biological crosslinking at 70-80°C for 2-4 hours; (d2) a step of forming a nanocomposite with a tensile strength improved by 30% or more by adding 0.3-0.7 parts by weight of graphene oxide per 100 parts by weight of the crosslinked chitosan and ultrasonically treating at a frequency of 20-30 kHz for 15-25 minutes; (d3) a step of imparting flexibility with an elongation improved by 50% or more when measured by the ASTM D638 test method by adding 15-25 parts by weight of epoxidized soybean oil, a vegetable oil-based plasticizer, per 100 parts by weight of the nanocomposite; (d4) per 100 parts by weight of the mixture, starch and The method is characterized by comprising: a step of forming a composition that is 90% or more biodegradable within 180 days when measured by ASTM D5338 test method by adding 30-40 parts by weight of a biodegradable auxiliary polymer blend mixed with polycaprolactone (PCL) in a 1:2 weight ratio; and (d5) a step of melt-mixing the mixture using a twin-screw extruder under conditions of 160-180℃ and 50-60rpm, extruding it into a pellet shape with a diameter of 3-5mm, and then drying it at 50-60℃ for 12-18 hours to produce a biodegradable plastic pellet having a moisture content of 1% or less when measured by weight.

[0043] Critical significance of the component range and manufacturing stage of each component

[0044] Reasons for selecting materials used in biodegradable plastics made from shrimp shell byproducts

[0045] Ultrasonic cleaning technology

[0046] The reason for introducing ultrasonic cleaning technology into the pretreatment process of shrimp shell byproducts in this invention is that it significantly improves the removal efficiency of foreign substances and proteins attached to the surface through the cavitation of microbubbles generated by ultrasound. Compared to conventional simple immersion or stirring methods, ultrasonic treatment (20-40 kHz) allows the cleaning solution to effectively penetrate even the micropores on the surface of the shrimp shells, thereby reducing the cleaning time by approximately 40% compared to conventional methods and reducing the amount of chemicals used. In addition, by treating at a temperature of 45-55°C, optimal conditions can be achieved to promote protein denaturation to increase removal efficiency while simultaneously minimizing the reduction of the molecular weight of chitin.

[0047] Enzyme complex (Alcalase® protease and Novozym® lipase)

[0048] In the present invention, an enzyme complex containing Alcalase® protease and Novozym® lipase in a 1:1 weight ratio was used in the process of extracting chitin from shrimp shells. This enzyme complex was selected because the protease effectively hydrolyzes proteins and the lipase decomposes lipids, thereby maximizing chitin extraction efficiency. Compared to the conventional high-concentration alkali (10-20% NaOH) treatment method, the enzymatic method is performed under mild conditions of 38-42°C in a near-neutral environment with a pH of 5.8-6.2, making it environmentally friendly and requiring less energy consumption. Furthermore, experimental results regarding various ratios confirmed that the 1:1 weight ratio combination of these two enzymes optimizes the purity and yield of chitin. By using commercially available enzymes, the reproducibility and economic feasibility of the process can be ensured.

[0049] Microwave-assisted deacetylation technology

[0050] In this invention, microwave-assisted deacetylation technology was adopted instead of the conventional hydrothermal treatment method for the deacetylation of chitin. Microwaves with a frequency of 2.45 GHz induce dipole rotation of water molecules in a sodium hydroxide solution, enabling efficient heat transfer at the molecular level. As a result, the reaction time is significantly reduced from the conventional 8-12 hours to 60-80 minutes (a total of 6-8 cycles with 5 minutes of irradiation followed by 2 minutes of rest as one cycle), and energy consumption is reduced by approximately 70%. Furthermore, microwave treatment allows for the selective removal of acetyl groups from chitin molecules, thereby increasing the degree of deacetylation of chitosan to over 85% while minimizing random cleavage of the polymer main chain, which has the advantage of enabling the production of high molecular weight chitosan of 150-250 kDa.

[0051] Ascorbic acid (antioxidant)

[0052] In the present invention, 0.5 to 1.5 parts by weight of ascorbic acid were added per 100 parts by weight of chitin to inhibit the reduction in molecular weight of chitosan during the deacetylation process. The deacetylation process proceeds under strong alkaline conditions, and during this process, cleavage of the main chain of chitosan due to oxidation reactions may occur. Ascorbic acid is a powerful reducing agent that inhibits oxidation reactions by effectively removing free radicals generated during the reaction. Experimental results on various antioxidants confirmed that ascorbic acid is water-soluble, has excellent biocompatibility, and inhibits the reduction in molecular weight of chitosan by more than 50% when added in the range of 0.5 to 1.5 parts by weight. Chitosan with preserved molecular weight has the effect of significantly improving the mechanical properties of the final biodegradable plastic.

[0053] Jennipin (natural crosslinking agent)

[0054] In this invention, gennipin, a natural crosslinking agent, was selected in an amount of 0.5 to 1.5 parts by weight per 100 parts by weight of chitosan for the crosslinking of chitosan. Gennipin is a natural iridoid glycoside extracted from the fruit of *Gardenia jasminoides*, which selectively reacts with the amino groups of chitosan to form stable crosslinks. Unlike conventional chemical crosslinking agents such as glutaraldehyde, gennipin has the advantages of excellent biocompatibility and biodegradability, as well as low toxicity. Through a crosslinking reaction at 70-80°C for 2 to 4 hours, the thermal stability of chitosan is improved by more than 20°C, and moisture resistance is significantly enhanced. Furthermore, the crosslinking by gennipin provides a balance point that improves the mechanical strength of the final biodegradable plastic while maintaining an appropriate biodegradation rate.

[0055] Graphene oxide (nanofiller)

[0056] In the present invention, 0.3 to 0.7 parts by weight of graphene oxide were added as a nanofiller to 100 parts by weight of cross-linked chitosan. Graphene oxide has various oxygen-containing functional groups (carboxyl groups, hydroxyl groups, epoxy groups, etc.) on its surface, which can form strong hydrogen bonds and ionic bonds with the amino and hydroxyl groups of chitosan. Ultrasonic treatment at a frequency of 20-30 kHz ensures that the graphene oxide is uniformly dispersed in the chitosan matrix, and the resulting nanocomposite exhibits an improvement in tensile strength of more than 30% and an increase in heat deformation temperature of more than 15°C. In particular, the addition amount of 0.3 to 0.7 parts by weight was confirmed through various concentration experiments to be the optimal range that satisfies both improved mechanical properties and appropriate biodegradability.

[0057] Epoxidized soybean oil (vegetable oil-based plasticizer)

[0058] In the present invention, 15 to 25 parts by weight of epoxidized soybean oil, a vegetable oil-based plasticizer, were added to 100 parts by weight of a nanocomposite. Epoxidized soybean oil is a bio-based plasticizer prepared by epoxidizing the unsaturated bonds of soybean oil; compared to petroleum-based phthalate plasticizers, it has lower toxicity and is environmentally friendly. The epoxy groups interact with the hydroxyl and amino groups of chitosan to weaken hydrogen bonds between chitosan molecules and increase the mobility of molecular chains, thereby imparting flexibility to the plastic. When measured by the ASTM D638 test method, the addition of epoxidized soybean oil improves the elongation rate by more than 50%, significantly improving flexibility and processability. Furthermore, epoxidized soybean oil has the advantage of being biodegradable, so it does not affect the biodegradability of the final plastic.

[0059] Starch and polycaprolactone (PCL) blend (biodegradable copolymer)

[0060] In the present invention, 30 to 40 parts by weight of a biodegradable auxiliary polymer blend, comprising starch and polycaprolactone (PCL) mixed in a 1:2 weight ratio, was added to 100 parts by weight of the mixture. Starch is an economical and completely biodegradable natural polymer, but it has the disadvantages of weak mechanical properties and vulnerability to moisture. On the other hand, PCL is a synthetic biodegradable polyester with excellent mechanical properties and moisture resistance, but it has a slow biodegradation rate. By blending these two materials in a 1:2 weight ratio, the disadvantages of each material can be mutually compensated for, and their advantages can be maximized. In particular, this blend exhibits excellent compatibility with chitosan, forming a uniform mixture without phase separation, and achieves an optimal biodegradation rate of over 90% within 180 days when measured by the ASTM D5338 test method. Furthermore, the addition amount of 30 to 40 parts by weight was confirmed through various experiments to be the optimal range that provides a balance of mechanical properties, processability, and biodegradability.

[0061] Critical Significance of the Manufacturing Method of Biodegradable Plastics Using Shrimp Shell By-products

[0062] Critical significance of sodium chloride aqueous solution concentration (0.5-1.5 parts by weight)

[0063] The concentration range of 0.5 to 1.5 parts by weight of the sodium chloride aqueous solution used in the present invention is a critical range that exhibits optimal efficiency in removing foreign substances from shrimp shell by-products. At a concentration of less than 0.5 parts by weight, the removal of microorganisms and organic matter attached to the surface of the shrimp shells is insufficient, acting as a factor that lowers the purity of chitin in subsequent processes. On the other hand, at a concentration exceeding 1.5 parts by weight, sodium chloride penetrates into the micropores of the shrimp shells and remains without being completely removed during the subsequent washing process, which may negatively affect the quality of the final product. Therefore, the concentration range of 0.5 to 1.5 parts by weight holds critical significance as a balance point between the efficiency of foreign substance removal and the quality of the final product.

[0064] Critical Significance of Ultrasonic Processing Frequency (20-40 kHz)

[0065] The frequency range of 20-40 kHz applied during the ultrasonic cleaning process is the optimal critical condition for effectively removing foreign substances from the surface of shrimp shells without damaging the molecular structure of chitin. At frequencies below 20 kHz, cavitation does not occur sufficiently, leading to reduced cleaning efficiency, while at frequencies exceeding 40 kHz, excessive energy destroys the glycosidic bonds of chitin molecules, causing a decrease in molecular weight. Experimental results confirmed that in the 20-40 kHz range, cleaning efficiency improved by 65% ​​compared to the conventional stirring method, while the reduction in chitin molecular weight was limited to within 5%.

[0066] Critical significance of ultrasonic treatment time (15-25 minutes)

[0067] The ultrasonic treatment time of 15 to 25 minutes is a critical time range that provides an optimal balance between the efficiency of foreign substance removal and energy consumption. Treatment times of less than 15 minutes result in incomplete removal of foreign substances, causing the purity of chitin to drop to less than 90%, while treatment exceeding 25 minutes only increases energy consumption while having minimal additional effect on foreign substance removal. Furthermore, ultrasonic treatment exceeding 25 minutes can cause excessive denaturation of proteins within the shrimp shells, which may actually make the subsequent protein removal process more difficult.

[0068] Critical significance of execution methods and stages

[0069] In this stage, ultrasonic cleaning was introduced to maximize the pretreatment efficiency of shrimp shell byproducts. Ultrasonic cleaning utilizes the mechanical energy generated during the formation and collapse of microbubbles produced by ultrasound, allowing the cleaning solution to effectively penetrate even the micropores of the shrimp shells compared to conventional simple immersion or stirring methods. This demonstrates excellent efficacy, particularly in removing microorganisms and surface-attached organic matter, making it a key factor in determining the purity and yield of the subsequent chitin extraction process. Furthermore, the use of an aqueous sodium chloride solution enables the effective removal of mineral impurities along with biological contamination, which directly influences the physical properties and transparency of the final biodegradable plastic.

[0070] Critical significance of hydrochloric acid solution concentration (1.8-2.2 parts by weight)

[0071] The concentration range of 1.8 to 2.2 parts by weight of the hydrochloric acid solution used for demineralization treatment is the optimal critical range that effectively removes calcium carbonate from shrimp shells while minimizing damage to the molecular structure of chitin. At a concentration below 1.8 parts by weight, the removal of calcium carbonate is incomplete, resulting in a final chitin purity of less than 90%, while at a concentration exceeding 2.2 parts by weight, partial hydrolysis of chitin occurs, causing a problem where the molecular weight decreases by more than 20%. Within this concentration range, a calcium carbonate removal rate of 98% or more is achieved while preserving the molecular structure of chitin.

[0072] Critical significance of the mixing ratio of ethanol and acetone (3:2)

[0073] The mixing ratio of ethanol and acetone (3:2) for pigment removal is a critical composition that provides an optimal balance between pigment removal efficiency and solvent consumption. If the ethanol ratio increases (exceeding 3:2), the solubility of fat-soluble pigments decreases, resulting in reduced color removal efficiency; if the acetone ratio increases (below 3:2), partial dissolution of chitin within the shrimp shell occurs, leading to a decrease in yield. Furthermore, the 3:2 ratio provides an optimal combination of the eco-friendliness of ethanol and the strong dissolving power of acetone, offering a balance between environmental burden and pigment removal efficiency.

[0074] Critical significance of the amount of enzyme complex added (2-5 parts by weight)

[0075] The addition amount range of 2 to 5 parts by weight of the enzyme complex is a critical range that represents the optimal balance between protein and lipid removal efficiency and economic feasibility. Adding less than 2 parts by weight results in incomplete removal of proteins and lipids, leading to a decrease in chitin purity; adding more than 5 parts by weight, while providing only minimal additional purity improvement, increases costs. Within this addition range, it is possible to simultaneously achieve a chitin purity of 92% or higher and a yield of 85% or higher.

[0076] Critical significance of execution methods and stages

[0077] In this stage, the efficiency and environmental friendliness of chitin extraction were maximized by combining chemical and enzymatic methods. Demineralization treatment using hydrochloric acid is an essential process for removing inorganic components (primarily calcium carbonate) from shrimp shells, and this determines the efficiency of subsequent steps. By using hydrochloric acid at an appropriate concentration during the demineralization process, the efficiency of inorganic removal can be maximized while minimizing damage to the molecular structure of chitin. The subsequent pigment removal process selectively removes carotenoid pigments using an optimal mixed solvent of ethanol and acetone, thereby expanding the visual quality and application range of the final product. Finally, the enzymatic extraction method is conducted under milder conditions compared to conventional strong alkaline treatments, preventing a decrease in chitin molecular weight and significantly reducing the use of chemicals, thereby mitigating the environmental burden. Through these stepwise treatments, efficiency, economic viability, and eco-friendliness in chitin extraction can be achieved simultaneously.

[0078] Critical significance of sodium hydroxide solution concentration (35-45 parts by weight)

[0079] The concentration range of 35 to 45 parts by weight of the sodium hydroxide solution for deacetylation is a critical range that provides a balance between the deacetylation efficiency of chitin and the preservation of molecular weight. At a concentration below 35 parts by weight, the degree of deacetylation is low, falling below 80%, which degrades the physical properties of the final chitosan; at a concentration exceeding 45 parts by weight, the glycosidic bonds of chitosan are hydrolyzed, leading to a significant decrease in molecular weight. Within this concentration range, a degree of deacetylation of 85% or more and a molecular weight of 150 kDa or more can be achieved simultaneously.

[0080] Critical significance of ascorbic acid addition amount (0.5-1.5 parts by weight)

[0081] The addition range of 0.5 to 1.5 parts by weight of ascorbic acid, an antioxidant, is a critical range that effectively inhibits the oxidation reaction occurring during the deacetylation process, thereby preventing a decrease in the molecular weight of chitosan. If less than 0.5 parts by weight is added, the antioxidant effect is insufficient, resulting in a molecular weight reduction of 40% or more; if more than 1.5 parts by weight is added, the deacetylation reaction itself is inhibited, leading to a decrease in the degree of deacetylation. Within this addition range, the decrease in molecular weight can be limited to within 20% without a decrease in the degree of deacetylation.

[0082] Critical Significance of Microwave Processing Conditions (600-800W, 6-8 Cycles)

[0083] The microwave power range of 600–800 W and the processing cycle range of 6–8 cycles represent critical conditions that provide an optimal balance between deacetylation efficiency and energy consumption. At power levels below 600 W, the deacetylation reaction proceeds incompletely, causing the degree of deacetylation to drop to less than 80%, while at power levels exceeding 800 W, localized overheating accelerates the decomposition of chitosan. Furthermore, processing with fewer than 6 cycles results in incomplete deacetylation, while processing exceeding 8 cycles only increases energy consumption without providing additional deacetylation effects. Within this condition range, it is possible to simultaneously achieve a degree of deacetylation of over 85% and a yield of over 90%.

[0084] Critical significance of execution methods and stages

[0085] In this step, microwave-assisted deacetylation technology was introduced to maximize the deacetylation efficiency of chitin and shorten the process time. Unlike conventional hot water heating methods, microwave heating enables direct energy transfer at the molecular level, significantly improving reaction efficiency. In particular, microwave energy selectively acts on the acetyl groups of chitin molecules to promote the deacetylation reaction while minimizing the hydrolysis of glycosidic bonds. Additionally, by setting a periodic resting time (2 minutes), a uniform heat distribution is induced and localized overheating is prevented, thereby preserving the molecular weight of chitosan. The addition of ascorbic acid is a key factor in suppressing oxidative degradation occurring under strong alkaline conditions, which enables the production of chitosan with a molecular weight more than 30% higher than that of conventional methods. The high molecular weight, high degree of deacetylation chitosan produced in this way is a key factor determining the mechanical properties and biocompatibility of the final biodegradable plastic.

[0086] Critical significance of the amount of zennipin added (0.5-1.5 parts by weight)

[0087] The addition range of 0.5 to 1.5 parts by weight of zennipin, a natural crosslinking agent, is the critical range that exhibits the optimal effect in improving the thermal stability and moisture resistance of chitosan. If less than 0.5 parts by weight is added, the crosslinking density is insufficient, resulting in a negligible improvement in heat resistance and water resistance; if more than 1.5 parts by weight is added, brittleness increases and flexibility decreases due to excessive crosslinking. Within this addition range, the heat deformation temperature is improved by more than 20°C, and the moisture absorption rate is reduced by more than 40% while maintaining appropriate flexibility.

[0088] Critical significance of graphene oxide addition amount (0.3-0.7 parts by weight)

[0089] The addition range of 0.3 to 0.7 parts by weight of graphene oxide, a nano-filler, is a critical range that provides a balance between improving mechanical properties and maintaining biodegradability. If added at less than 0.3 parts by weight, the effect of improving mechanical properties is negligible, and if added at more than 0.7 parts by weight, aggregation of graphene oxide occurs, which actually degrades properties and significantly reduces the biodegradation rate. Within this addition range, tensile strength is improved by more than 30%, and the reduction in the biodegradation rate is limited to within 10%.

[0090] Critical significance of the amount of epoxidized soybean oil added (15-25 parts by weight)

[0091] The addition range of 15 to 25 parts by weight of epoxidized soybean oil, which is a plasticizer, is a critical range that provides an optimal balance of flexibility and mechanical strength. If less than 15 parts by weight is added, the plasticizing effect is insufficient, resulting in high brittleness and reduced processability; if more than 25 parts by weight are added, mechanical strength decreases significantly and phase separation may occur. Within this addition range, the elongation rate is improved by more than 50%, while the decrease in tensile strength is limited to within 15%.

[0092] Critical significance of the amount of biodegradable auxiliary polymer blend added (30-40 parts by weight)

[0093] The addition range of 30 to 40 parts by weight of the starch and polycaprolactone blend is a critical range that provides an optimal balance of processability, mechanical properties, and biodegradability. If less than 30 parts by weight is added, the effect of improving processability is negligible, and if more than 40 parts by weight are added, the characteristics of the chitosan matrix are weakened, resulting in a decrease in antibacterial properties and mechanical properties. Within this addition range, melt processability is significantly improved, and the biodegradation rate is optimized to over 90% within 180 days.

[0094] Critical significance of execution methods and stages

[0095] In this stage, the physical properties of chitosan-based biodegradable plastics were comprehensively enhanced by integrating biological crosslinking, nanocompositing, plasticization, and polymer blending technologies. Biological crosslinking using zennipin is a key technology that effectively improves the heat and water resistance of chitosan while maintaining biocompatibility and biodegradability, unlike conventional chemical crosslinking agents. Nano-filling with graphene oxide significantly enhances mechanical strength as nanoparticles uniformly dispersed within the chitosan matrix act as stress transfer media; this is an essential element for the practical application of chitosan-based plastics. The addition of epoxidized soybean oil weakens the interactions between the molecular chains of chitosan, thereby imparting flexibility and improving processability; furthermore, the use of vegetable oil-based plasticizers maintains environmental friendliness. Finally, the addition of a starch and polycaprolactone blend enables the thermoplastic processing of chitosan and optimizes the biodegradation rate, playing a decisive role in realizing biodegradable plastic materials suitable for actual industrial applications. This multi-stage composite process synergistically combines the advantages of each component, enabling comprehensive improvement in physical properties that is difficult to achieve with a single material.

[0096] Critical significance of step 6 (e)

[0097] Critical significance of the melting mixing temperature (160-180℃)

[0098] The melt mixing temperature range of 160-180°C using a twin-screw extruder is a critical range that provides a balance between the uniform mixing of the composite material and the prevention of thermal decomposition. At temperatures below 160°C, the melting of the polycaprolactone and chitosan composite is incomplete, failing to form a uniform mixture, while at temperatures exceeding 180°C, thermal decomposition of chitosan and starch proceeds, degrading the physical properties of the final product. Within this temperature range, uniform mixing is achieved while the degradation of physical properties due to thermal decomposition is limited to within 5%.

[0099] Critical significance of screw rotation speed (50-60 rpm)

[0100] The rotational speed range of 50-60 rpm for the twin-screw extruder is a critical range that provides a balance point between mixing efficiency and polymer chain cleavage due to shear stress. At speeds below 50 rpm, mixing is insufficient, which may lead to phase separation, while at speeds exceeding 60 rpm, excessive shear stress causes a decrease in the molecular weight of chitosan and PCL, resulting in a deterioration of mechanical properties. Within this speed range, uniform mixing is achieved while the reduction in molecular weight is limited to within 10%.

[0101] Critical Significance of Pellet Drying Conditions (50-60℃, 12-18 hours)

[0102] The temperature range of 50–60°C and the time range of 12–18 hours for pellet drying represent critical conditions that provide a balance between moisture removal efficiency and prevention of degradation. At temperatures below 50°C, moisture removal is insufficient, leading to the formation of bubbles during the subsequent molding process, while temperatures exceeding 60°C may result in oxidation of the epoxidized soybean oil and discoloration of the chitosan. Furthermore, drying for less than 12 hours causes the moisture content to exceed 1%, degrading product quality, while drying for more than 18 hours only increases energy consumption without any additional moisture reduction effect. Within this condition range, it is possible to simultaneously achieve a moisture content of 1% or less and minimal degradation.

[0103] Critical significance of execution methods and stages

[0104] In this stage, uniform mixing of composite materials and thermoplastic processing were achieved by utilizing twin-screw extrusion technology. The twin-screw extruder provides both dispersion and distribution mixing simultaneously, enabling the uniform dispersion of graphene oxide, a nano-filler, and the effective mixing of various polymeric components (chitosan, starch, and PCL). In particular, the co-rotation structure of the twin-screw applies appropriate shear stress to the mixture, allowing for the formation of a uniform composite without phase separation. Furthermore, the temperature profile (160–180°C) set during the extrusion process provides optimal mixing conditions by ensuring the complete melting of PCL while minimizing the decomposition of heat-sensitive components such as chitosan. By manufacturing the material into pellets after extrusion and drying it under appropriate conditions, processability in subsequent molding processes is improved, and moisture content—a critical factor determining the quality of the final product—is strictly controlled. Through such precise process control, it is possible to stably manufacture biodegradable plastic materials with comprehensively optimized mechanical properties, biodegradability, and processability.

[0105] Examples and Comparative Examples

[0106] Examples and comparative examples regarding a method for manufacturing biodegradable plastic using shrimp shell by-products

[0107] 1. Composition of Examples and Comparative Examples

[0108] (a) Step: Examples and comparative examples regarding the pretreatment of shrimp shell by-products division Sodium chloride concentration (parts by weight) Ultrasonic frequency (kHz) Ultrasonic treatment time (minutes) Sodium hydroxide concentration (parts by weight) Washing pH Drying conditions (°C, time) Example 1 0.5 20 15 0.8 6.8 60, 12 Example 2 1.0 30 20 1.0 7.0 65, 10 Example 3 1.5 40 25 1.2 7.2 70, 8 Comparative Example 1 0.3 10 10 0.5 6.5 55, 14 Comparative Example 2 2.0 50 30 1.5 7.5 75, 6 Comparative Example 3 - - 60 (stirring) 5.0 8.0 80, 5

[0109] In Examples 1-3 of the present invention, shrimp shell byproducts were pretreated under conditions of a sodium chloride concentration of 0.5-1.5 parts by weight, an ultrasonic frequency of 20-40 kHz, and an ultrasonic treatment time of 15-25 minutes. In Comparative Example 1, the sodium chloride concentration (0.3 parts by weight), the ultrasonic frequency (10 kHz), and the treatment time (10 minutes) were all set below the lower limit of the claim, and in Comparative Example 2, the sodium chloride concentration (2.0 parts by weight), the ultrasonic frequency (50 kHz), and the treatment time (30 minutes) were all set to exceed the upper limit of the claim. In Comparative Example 3, a conventional stirring method (60 minutes) was applied instead of ultrasonic treatment, and a high concentration of sodium hydroxide (5.0 parts by weight) was used.

[0110] (a) Step: Analysis of results from examples and comparative examples division Impurity removal rate (%) Protein removal rate (%) Chitin purity (%) Shrimp shell color Process time (time) Example 1 92.5 94.3 91.8 light white 15 Example 2 95.8 96.7 93.5 white 13 Example 3 97.2 97.9 94.7 white 11 Comparative Example 1 85.3 88.5 87.2 pale yellow 17 Comparative Example 2 97.5 98.1 94.8 white 10 Comparative Example 3 93.1 95.2 90.1 yellow 23

[0111] Analysis of the results of Examples 1-3 confirms that as the sodium chloride concentration, ultrasonic frequency, and processing time increase, the removal rates of impurities and proteins improve, and the purity of chitin tends to increase. In particular, Example 2 (1.0 wt. of sodium chloride, 30 kHz ultrasonic, 20 min) demonstrated an optimal balance between efficient impurity removal (95.8%) and processing time (13 hours). In Comparative Example 1, due to insufficient processing conditions, the impurity removal rate was only 85.3%, resulting in a low final chitin purity of 87.2%; furthermore, the color was light yellow, indicating a degradation in quality. Comparative Example 2 showed an impurity removal rate (97.5%) and chitin purity (94.8%) similar to Example 3, but a problem was identified where the molecular weight of the chitin decreased by 15% due to excessive processing conditions (molecular weight data not included in the table). In the case of Comparative Example 3, the process time increased significantly to 23 hours due to the stirring method, and the problem occurred that the final product turned yellow due to the use of a high concentration of sodium hydroxide.

[0112] (b) Step: Examples and comparative examples regarding chitin extraction division Hydrochloric acid concentration (parts by weight) Extraction solvent ratio (ethanol:acetone) Amount of enzyme complex added (parts by weight) Enzyme reaction conditions (°C, pH) Centrifugation conditions (rpm, min) Drying conditions (°C, time) Example 4 1.8 3:2 2 38, 5.8 5000, 20 45, 14 Example 5 2.0 3:2 3.5 40, 6.0 5500, 25 50, 12 Example 6 2.2 3:2 5 42, 6.2 6000, 30 55, 10 Comparative Example 4 1.5 2:3 1 35, 5.5 4500, 15 40, 16 Comparative Example 5 2.5 4:1 6 45, 6.5 6500, 35 60, 8 Comparative Example 6 5.0 - - 80, 11.0 5000, 30 50, 12

[0113] In Examples 4-6 of the present invention, chitin was extracted under conditions of a hydrochloric acid concentration of 1.8-2.2 parts by weight, an ethanol:acetone ratio of 3:2, and an enzyme complex addition amount of 2-5 parts by weight. In Comparative Example 4, the hydrochloric acid concentration (1.5 parts by weight), the enzyme addition amount (1 part by weight), and the reaction temperature (35°C) were all set below the lower limit of the claims, while in Comparative Example 5, the hydrochloric acid concentration (2.5 parts by weight), the enzyme addition amount (6 parts by weight), and the reaction temperature (45°C) were all set to exceed the upper limit of the claims. In Comparative Example 6, a conventional chemical method (5.0 parts by weight hydrochloric acid, strong alkaline conditions of pH 11.0) was applied instead of the enzymatic method.

[0114] (b) Step: Analysis of results from examples and comparative examples division Calcium carbonate removal rate (%) Pigment removal rate (%) Protein Residual Rate (%) Chitin purity (%) Chitin Yield (%) Energy consumption (relative value) Example 4 96.3 92.8 1.8 92.5 87.3 0.65 Example 5 98.1 95.3 1.2 94.8 85.7 0.70 Example 6 99.2 97.5 0.8 96.2 83.5 0.75 Comparative Example 4 91.5 84.3 3.5 88.7 89.2 0.60 Comparative Example 5 99.5 98.2 0.6 96.5 78.3 0.85 Comparative Example 6 99.3 90.5 1.5 94.5 70.2 1.00

[0115] Analyzing the results of Examples 4-6, it can be confirmed that as the hydrochloric acid concentration and the amount of enzyme complex added increase, the removal rate of calcium carbonate and pigment improves and the protein retention rate decreases, leading to a tendency for chitin purity to increase. In particular, Example 5 (2.0 parts by weight of hydrochloric acid, 3.5 parts by weight of enzyme) showed an optimal balance between high chitin purity (94.8%) and yield (85.7%). In Comparative Example 4, due to insufficient processing conditions, the calcium carbonate removal rate was only 91.5%, resulting in a low final chitin purity of 88.7%. Comparative Example 5 showed chitin purity (96.5%) similar to Example 6, but it was confirmed that the chitin yield decreased to 78.3% due to excessive processing conditions. In the case of Comparative Example 6, energy consumption increased by 30-40% compared to the examples due to the application of a chemical method, and the chitin yield decreased significantly to 70.2%.

[0116] (c) Step: Examples and comparative examples regarding the preparation of chitosan division Sodium hydroxide concentration (parts by weight) Amount of ascorbic acid added (parts by weight) Microwave output (W) Number of processing cycles Acetic acid concentration (parts by weight) Filtration conditions (μm) Example 7 35 0.5 600 6 0.8 0.45 Example 8 40 1.0 700 7 1.0 0.45 Example 9 45 1.5 800 8 1.2 0.45 Comparative Example 7 30 0.3 500 5 0.6 0.80 Comparative Example 8 50 2.0 900 9 1.5 0.22 Comparative Example 9 45 - - (Hydrothermal treatment, 8 hours) - 1.0 0.45

[0117] In Examples 7-9 of the present invention, chitosan was prepared by deacetylating chitin under conditions of a sodium hydroxide concentration of 35-45 parts by weight, an ascorbic acid addition amount of 0.5-1.5 parts by weight, a microwave output of 600-800 W, and 6-8 treatment cycles. In Comparative Example 7, the sodium hydroxide concentration (30 parts by weight), the ascorbic acid addition amount (0.3 parts by weight), and the microwave output (500 W) were all set below the lower limit of the claim, while in Comparative Example 8, the sodium hydroxide concentration (50 parts by weight), the ascorbic acid addition amount (2.0 parts by weight), and the microwave output (900 W) were all set to exceed the upper limit of the claim. In Comparative Example 9, a conventional hydrothermal treatment method (8 hours) was applied instead of microwave treatment, and ascorbic acid was not added.

[0118] (c) Step: Analysis of results from examples and comparative examples division Degree of deacetylation (%) Chitosan molecular weight (kDa) Chitosan Yield (%) Chitosan Whiteness (%) Process time (minutes) Energy consumption (relative value) Example 7 85.3 220 92.5 93.2 78 0.55 Example 8 88.7 195 90.3 94.8 74 0.60 Example 9 91.5 175 88.7 95.5 70 0.65 Comparative Example 7 78.2 235 94.1 90.5 82 0.50 Comparative Example 8 93.2 120 83.5 96.2 68 0.75 Comparative Example 9 86.5 130 87.2 92.3 480 1.00

[0119] Analysis of the results of Examples 7-9 reveals a tendency for the degree of deacetylation to increase and the molecular weight to decrease as the sodium hydroxide concentration and microwave power increase. In particular, Example 8 (40 parts by weight of sodium hydroxide, 1.0 part by weight of ascorbic acid, microwave power 700W) showed an optimal balance point between the degree of deacetylation (88.7%) and the molecular weight (195 kDa). It was confirmed that the addition of ascorbic acid effectively inhibits the decrease in the molecular weight of chitosan during the deacetylation process.

[0120] In Comparative Example 7, the degree of deacetylation was limited to 78.2% due to insufficient processing conditions, resulting in a deterioration of the physical properties of chitosan. Comparative Example 8 showed a high degree of deacetylation (93.2%), but it was confirmed that the molecular weight of chitosan decreased significantly to 120 kDa due to excessive processing conditions. In the case of Comparative Example 9, the process time increased significantly to 480 minutes (8 hours) by applying a hydrothermal treatment method instead of microwave treatment, and the molecular weight decreased to 130 kDa due to the absence of ascorbic acid. In terms of energy consumption, Examples 7-9 showed a 35-45% reduction effect compared to Comparative Example 9.

[0121] Of particular note is that, under all conditions of the examples, the synergistic effect of microwave treatment and ascorbic acid addition enabled the production of high-quality chitosan by significantly reducing the treatment time compared to conventional methods (480 min → 70-78 min) while effectively suppressing the reduction in molecular weight (130 kDa → 175-220 kDa).

[0122] (d) Step: Examples and comparative examples regarding chitosan complexation division Amount of Jennipin added (parts by weight) Amount of graphene oxide added (parts by weight) Amount of epoxidized soybean oil added (parts by weight) Starch:PCL Blend Addition Amount (parts by weight) Extrusion temperature (°C) Extrusion speed (rpm) Example 10 0.5 0.3 15 30 160 50 Example 11 1.0 0.5 20 35 170 55 Example 12 1.5 0.7 25 40 180 60 Comparative Example 10 0.3 0.2 10 25 150 45 Comparative Example 11 2.0 1.0 30 45 190 65 Comparative Example 12 - - 20 35 170 55

[0123] In Examples 10-12 of the present invention, a chitosan-based biodegradable plastic was prepared under conditions of 0.5-1.5 parts by weight of zennipin, 0.3-0.7 parts by weight of graphene oxide, 15-25 parts by weight of epoxidized soybean oil, and 30-40 parts by weight of starch:PCL blend. In Comparative Example 10, the amounts of each additive were all set below the lower limit of the claim, while in Comparative Example 11, they were all set to exceed the upper limit of the claim. In Comparative Example 12, zennipin and graphene oxide were not added, and other conditions were applied identically to those in Example 11.

[0124] (d) Step: Analysis of results from examples and comparative examples division Tensile strength (MPa) Growth rate (%) Heat distortion temperature (°C) Water absorption rate (%) Biodegradation rate (%, 180 days) transparency(%) Example 10 35.8 152 95.3 15.2 95.3 82.5 Example 11 42.5 185 102.7 12.5 92.8 78.3 Example 12 48.3 210 108.5 10.3 90.2 75.1 Comparative Example 10 28.2 125 88.5 18.7 97.5 85.2 Comparative Example 11 50.5 105 112.3 8.5 65.3 68.7 Comparative Example 12 25.3 172 85.2 28.5 93.5 80.2

[0125] Analyzing the results of Examples 10-12, it can be observed that as the amount of gennipin and graphene oxide added increases, the tensile strength and heat distortion temperature improve, and the water absorption rate decreases. As the amount of epoxidized soybean oil added increases, the elongation rate improves, but the biodegradability showed a tendency to decrease slightly.

[0126] In particular, Example 11 (1.0 parts by weight of gennipin, 0.5 parts by weight of graphene oxide, 20 parts by weight of epoxidized soybean oil, 35 parts by weight of starch:PCL blend) showed an optimal balance point between tensile strength (42.5 MPa), elongation (185%), and biodegradability (92.8%). Compared to a pure chitosan film (data not shown), the tensile strength was improved by about 140% and the elongation increased by about 370%.

[0127] In Comparative Example 10, the physical properties were degraded due to low tensile strength (28.2 MPa) and heat distortion temperature (88.5°C) caused by insufficient additive content. Comparative Example 11 showed high tensile strength (50.5 MPa) and heat distortion temperature (112.3°C), but it was confirmed that the elongation decreased to 105% and the biodegradability decreased significantly to 65.3% due to excessive additive content. In the case of Comparative Example 12, the tensile strength was low at 25.3 MPa and the water absorption rate increased significantly to 28.5% due to the absence of gennipin and graphene oxide, resulting in reduced water resistance.

[0128] (e) Step: Examples and comparative examples regarding biodegradable plastic molding division Plastic surgery methods Mold temperature (°C) Injection pressure (MPa) Cooling time (seconds) Post-processing method Example 13 Injection molding 130 15 30 Natural drying Example 14 compression molding 150 10 45 UV surface treatment Example 15 blow molding 140 8 40 Hot air drying Comparative Example 13 Injection molding 110 10 20 Natural drying Comparative Example 14 Injection molding 190 20 60 Natural drying Comparative Example 15 Extrusion molding 170 - - Unprocessed

[0129] In Examples 13-15 of the present invention, chitosan-based biodegradable plastic products were manufactured by applying various molding methods (injection, compression, blow). The mold temperature was set to 130-150°C, the injection pressure to 8-15 MPa, and the cooling time to 30-45 seconds. In Comparative Examples 13-14, the molding conditions were set to be below the lower limit or above the upper limit of the claims, respectively, and in Comparative Example 15, an extrusion molding method was applied and no post-treatment was performed.

[0130] (e) Step: Analysis of results from examples and comparative examples division Surface quality (1-5 points) Dimensional stability (%) Impact resistance (J / m) Surface moisture resistance (contact angle, °) Product Yield (%) Example 13 4.5 98.3 52.3 83.5 95.8 Example 14 4.8 99.1 48.7 92.3 97.2 Example 15 4.3 97.5 45.2 85.7 94.5 Comparative Example 13 3.2 95.2 42.5 80.3 90.3 Comparative Example 14 3.8 96.8 50.2 84.2 85.7 Comparative Example 15 2.5 92.5 35.8 75.5 88.2

[0131] Analyzing the results of Examples 13-15, it can be confirmed that when appropriate molding conditions and post-processing methods are applied, products with excellent surface quality (4.3-4.8 points), dimensional stability (97.5-99.1%), and impact resistance (45.2-52.3 J / m) are manufactured. In particular, Example 14 (compression molding, UV surface treatment) had the best surface quality (4.8 points) and surface moisture resistance (92.3°), and the highest product yield (97.2%).

[0132] In Comparative Example 13, due to the low mold temperature (110℃) and injection pressure (10MPa), filling was incomplete and surface quality (3.2 points) deteriorated. In Comparative Example 14, it was confirmed that the product yield decreased to 85.7% due to thermal decomposition caused by the excessive mold temperature (190℃). In the case of Comparative Example 15, due to the application of the extrusion molding method and the failure to perform post-treatment, surface quality (2.5 points), dimensional stability (92.5%), impact resistance (35.8J / m), and surface moisture resistance (75.5°) all deteriorated, resulting in significantly reduced marketability.

[0133] Synthesizing the above results, it can be seen that appropriate mold temperature, injection pressure, cooling time, and post-treatment methods are key factors determining the quality and yield of the final product in the molding of biodegradable plastics. In particular, post-treatment processes such as UV surface treatment were identified as important steps that significantly improve surface moisture resistance, thereby enhancing the durability and practicality of the product.

[0134] 2. Analysis of the Critical Effects and Significance of Component Content at Each Stage

[0135] 2-1. (a) Step: Critical effect on the pretreatment of shrimp shell by-products

[0136] The critical effect of the sodium chloride concentration (0.5-1.5 parts by weight) in the pretreatment step can be analyzed through the results of Comparative Example 1 (0.3 parts by weight) and Comparative Example 2 (2.0 parts by weight). According to the results of Examples 1-3, in the sodium chloride concentration range of 0.5-1.5 parts by weight, the impurity removal rate was excellent at 92.5-97.2%, and the chitin purity was maintained at a high level of 91.8-94.7%. On the other hand, in Comparative Example 1, the sodium chloride concentration was applied at 0.3 parts by weight, which is less than 0.5 parts by weight, resulting in a low impurity removal rate of 85.3% and a chitin purity of only 87.2%. This is because the ionic strength was insufficient, which prevented the effective removal of impurities and microorganisms from the surface of the shrimp shells.

[0137] In Comparative Example 2, the sodium chloride concentration was applied at 2.0 parts by weight, exceeding 1.5 parts by weight, and the impurity removal rate (97.5%) was similar to that of Example 3 (97.2%); however, molecular weight measurement results confirmed that the molecular weight of chitin decreased by 15% due to the excessive salt concentration. This is analyzed to be because hydrogen bonds between chitin molecules were weakened and hydrolysis was promoted at high salt concentrations.

[0138] The critical effects of ultrasonic treatment frequency and time also showed a similar pattern. A frequency of 20-40 kHz and a treatment time of 15-25 minutes provided an optimal balance point for efficient impurity removal and maintenance of the chitin structure. In particular, compared to Comparative Example 3 (stirring method, 60 minutes), ultrasonic treatment (Examples 1-3) achieved a similar or superior impurity removal effect while reducing the process time by more than 50%.

[0139] The shrimp shell pretreatment method of the present invention has been proven to simultaneously achieve improved process efficiency and reduced energy consumption by introducing ultrasonic technology, and in particular, it has been confirmed that the range of sodium chloride concentration 0.5-1.5 parts by weight, ultrasonic frequency 20-40 kHz, and treatment time 15-25 minutes is a technically important critical range.

[0140] 2-2. (b) Step: Critical effect regarding chitin extraction

[0141] The critical effect of hydrochloric acid concentration (1.8-2.2 parts by weight) in the chitin extraction step is clearly revealed through the results of Comparative Example 4 (1.5 parts by weight) and Comparative Example 5 (2.5 parts by weight). According to the results of Examples 4-6, in the hydrochloric acid concentration range of 1.8-2.2 parts by weight, the calcium carbonate removal rate was excellent at 96.3-99.2%, the chitin purity was maintained at a high level of 92.5-96.2%, and the yield was also good at 83.5-87.3%.

[0142] In Comparative Example 4, the hydrochloric acid concentration was applied at 1.5 parts by weight, which is less than 1.8 parts by weight, resulting in a calcium carbonate removal rate of only 91.5% and a decrease in chitin purity to 88.7%. This is because the acid concentration was insufficient, failing to completely dissolve the calcium carbonate within the shrimp shells. On the other hand, in Comparative Example 5, the hydrochloric acid concentration was applied at 2.5 parts by weight, which exceeds 2.2 parts by weight; while the calcium carbonate removal rate (99.5%) was excellent, the chitin yield was 78.3%, a decrease of 5-9% compared to the example. This is analyzed to be due to partial hydrolysis of chitin caused by the excessive acid concentration.

[0143] The critical effect of the amount of enzyme complex added (2-5 parts by weight) is also noteworthy. In Comparative Example 4 (1 part by weight), the amount of enzyme was insufficient, resulting in a high protein retention rate of 3.5%, while in Comparative Example 5 (6 parts by weight), the yield decreased due to partial decomposition of the chitin itself caused by excessive enzyme addition. In particular, compared to Comparative Example 6 (chemical method), the enzymatic method (Examples 4-6) showed an effect of improving chitin yield by 10-17% while reducing energy consumption by 25-35%.

[0144] The mixing ratio of ethanol and acetone (3:2) was confirmed to be the optimal condition in terms of pigment removal rate and solvent economy. In Comparative Example 4 (2:3), the pigment removal rate was reduced to 84.3% due to the high ratio of acetone, and in Comparative Example 5 (4:1), the problem of reduced chitin yield due to the high ratio of ethanol was confirmed.

[0145] The chitin extraction method of the present invention has been proven to maximize the purity and yield of chitin and reduce environmental burden by optimally combining enzymatic and chemical methods, and in particular, it has been confirmed that the range of hydrochloric acid concentration 1.8-2.2 parts by weight and enzyme addition amount 2-5 parts by weight is a technically important critical range.

[0146] 2-3. (c) Step: Critical effect regarding chitosan production

[0147] The critical effect of the sodium hydroxide concentration (35-45 parts by weight) in the chitosan manufacturing step can be analyzed through the results of Comparative Example 7 (30 parts by weight) and Comparative Example 8 (50 parts by weight). According to the results of Examples 7-9, in the sodium hydroxide concentration range of 35-45 parts by weight, the degree of deacetylation was excellent at 85.3-91.5%, and the molecular weight of chitosan was maintained high at 175-220 kDa.

[0148] In Comparative Example 7, the sodium hydroxide concentration was applied at 30 parts by weight, which is less than 35 parts by weight, resulting in a low degree of deacetylation of 78.2% and a deterioration in the physical properties of the final chitosan. When the degree of deacetylation is less than 80%, the solubility and reactivity of chitosan decrease significantly, negatively affecting the physical properties of the biodegradable plastic. On the other hand, in Comparative Example 8, the sodium hydroxide concentration was applied at 50 parts by weight, which exceeds 45 parts by weight; although the degree of deacetylation (93.2%) was excellent, the molecular weight of chitosan decreased by 31-45% compared to the example to 120 kDa. This is analyzed to be due to the cleavage of glycosidic bonds occurring simultaneously with the deacetylation reaction caused by the excessive alkali concentration.

[0149] The effect of adding ascorbic acid is clearly demonstrated through a comparison with Comparative Example 9 (no addition). In Examples 7-9, 0.5-1.5 parts by weight of ascorbic acid were added to maintain the molecular weight of chitosan at 175-220 kDa, whereas in Comparative Example 9, the molecular weight decreased to 130 kDa due to the absence of ascorbic acid. This proves that ascorbic acid plays a role in protecting the molecular structure of chitosan by effectively inhibiting the oxidation reaction that occurs during the deacetylation process.

[0150] The critical effect of microwave treatment conditions (600-800W, 6-8 cycles) is also noteworthy. In Comparative Example 7 (500W, 5 cycles), the degree of deacetylation was low at 78.2% due to insufficient microwave energy, and in Comparative Example 8 (900W, 9 cycles), the molecular weight decreased significantly due to excessive energy input. In particular, compared to Comparative Example 9 (hydrothermal treatment, 8 hours), microwave treatment (Examples 7-9) was confirmed to have an excellent molecular weight preservation effect while shortening the process time by approximately 85%.

[0151] The chitosan manufacturing method of the present invention has been proven to simultaneously achieve improved process efficiency and high-quality chitosan production through microwave-assisted deacetylation technology and the addition of antioxidants, and in particular, it has been confirmed that the range of sodium hydroxide concentration 35-45 parts by weight, ascorbic acid addition amount 0.5-1.5 parts by weight, microwave power 600-800W, and 6-8 processing cycles is a technically important critical range.

[0152] 2-4. (d) Step: Critical effect regarding chitosan complexation

[0153] The critical effect of the amount of zennipin added (0.5-1.5 parts by weight) in the chitosan complexation step can be analyzed through the results of Comparative Example 10 (0.3 parts by weight), Comparative Example 11 (2.0 parts by weight), and Comparative Example 12 (no addition). According to the results of Examples 10-12, in the range of 0.5-1.5 parts by weight of zennipin added, the tensile strength was excellent at 35.8-48.3 MPa and the heat distortion temperature was maintained at a high level of 95.3-108.5℃.

[0154] In Comparative Example 10, the amount of gennipin added was applied at 0.3 parts by weight, which is less than 0.5 parts by weight; as a result, the crosslinking density was insufficient, and the tensile strength decreased to 28.2 MPa. On the other hand, in Comparative Example 11, the amount of gennipin added was applied at 2.0 parts by weight, which exceeds 1.5 parts by weight; although the tensile strength (50.5 MPa) was high, the elongation decreased to 105% and the biodegradability decreased significantly to 65.3% due to excessive crosslinking. This is analyzed to be because the flexibility of the chitosan molecules was reduced and the accessibility for enzymatic biodegradation decreased due to excessive crosslinking. In particular, compared to Comparative Example 12 (no gennipin added), the addition of gennipin (Examples 10-12) showed an effect of improving tensile strength by 41-91% and reducing water absorption by 47-64%.

[0155] The critical effect of the graphene oxide addition amount (0.3-0.7 parts by weight) also showed a similar pattern. In Comparative Example 10 (0.2 parts by weight), the graphene oxide addition amount was insufficient, so the effect of improving tensile strength and heat distortion temperature was negligible, and in Comparative Example 11 (1.0 parts by weight), the biodegradability rate decreased significantly due to excessive addition. In addition, through comparison with Comparative Example 12 (no addition), it was confirmed that the addition of graphene oxide (Examples 10-12) has the effect of improving the heat distortion temperature by 10-23℃.

[0156] The critical effects of the amount of epoxylated soybean oil added (15-25 parts by weight) and the amount of starch:PCL blend added (30-40 parts by weight) were also clearly evident. In Comparative Example 10 (10 parts by weight of epoxylated soybean oil, 25 parts by weight of starch:PCL blend), the amount added was insufficient, resulting in reduced elongation and processability, while in Comparative Example 11 (30 parts by weight of epoxylated soybean oil, 45 parts by weight of starch:PCL blend), excessive addition caused problems such as reduced tensile strength, reduced transparency, and reduced biodegradability.

[0157] The chitosan composite method of the present invention has demonstrated that the physical properties of chitosan-based biodegradable plastics can be comprehensively improved by optimally combining biological crosslinking using zennipin, graphene oxide nanofilling, epoxidized soybean oil plasticization, and starch-PCL blending. In particular, it was confirmed that the content range of each additive is a technically critical range that provides a balance between improving physical properties and maintaining biodegradability.

[0158] 2-5. (e) Step: Critical effects regarding the molding of biodegradable plastics

[0159] The critical effect of the mold temperature (130-150°C) in the biodegradable plastic molding step can be analyzed through the results of Comparative Example 13 (110°C) and Comparative Example 14 (190°C). According to the results of Examples 13-15, in the mold temperature range of 130-150°C, the surface quality was excellent with a score of 4.3-4.8 and the product yield was maintained at a high level of 94.5-97.2%.

[0160] In Comparative Example 13, the mold temperature was applied at 110°C, which is less than 130°C, resulting in reduced fluidity of the melt and incomplete filling, leading to a low surface quality score of 3.2 and a decrease in product yield to 90.3%. On the other hand, in Comparative Example 14, the mold temperature was applied at 190°C, which exceeds 150°C, causing thermal decomposition of chitosan and a significant decrease in product yield to 85.7%. This is analyzed to be because chitosan and starch have heat-sensitive properties, causing rapid degradation when the temperature deviates from the appropriate range.

[0161] The effects of the molding method and post-treatment process are also noteworthy. Compared to Comparative Example 15 (extrusion molding, untreated), Examples 13-15 showed improved surface quality, dimensional stability, impact resistance, and surface moisture resistance by applying appropriate post-treatment along with injection, compression, and blow molding methods. In particular, UV surface treatment (Example 14) significantly improved surface moisture resistance, increasing the contact angle to 92.3°. This is analyzed to be due to the increased cross-linking density on the surface caused by UV irradiation, which improved hydrophobicity.

[0162] The biodegradable plastic molding method of the present invention has been proven to optimize the quality and performance of the product through appropriate molding conditions and post-processing steps, and in particular, it has been confirmed that the mold temperature range of 130-150°C is a technically important critical range that provides a balance point between melt fluidity and prevention of deterioration.

[0163] 3. Comprehensive Analysis and Conclusion

[0164] Analysis of the embodiments and comparative examples of the present invention confirmed that the critical range of key variables at each process stage is a critical factor determining the quality and performance of the final product in the manufacture of biodegradable plastics utilizing shrimp shell byproducts. In particular, by introducing innovative technologies such as ultrasonic pretreatment, enzymatic chitin extraction, microwave-assisted deacetylation, biological crosslinking, and nanocompositing, it was possible to simultaneously achieve improved process efficiency and product quality.

[0165] In the shrimp shell pretreatment step, conditions of a sodium chloride concentration of 0.5-1.5 parts by weight, an ultrasonic frequency of 20-40 kHz, and a treatment time of 15-25 minutes provided an optimal balance between impurity removal efficiency and the preservation of the molecular structure of chitin. In the chitin extraction step, conditions of a hydrochloric acid concentration of 1.8-2.2 parts by weight, an ethanol:acetone ratio of 3:2, and an enzyme complex addition amount of 2-5 parts by weight maximized the purity and yield of chitin.

[0166] In the chitosan manufacturing step, it was confirmed that conditions of a sodium hydroxide concentration of 35-45 parts by weight, an ascorbic acid addition amount of 0.5-1.5 parts by weight, a microwave power of 600-800W, and 6-8 processing cycles were optimal conditions for efficiently manufacturing high-quality chitosan. In the chitosan complexation step, conditions of an addition amount of 0.5-1.5 parts by weight of zennipin, an addition amount of 0.3-0.7 parts by weight of graphene oxide, an addition amount of 15-25 parts by weight of epoxidized soybean oil, and an addition amount of 30-40 parts by weight of starch:PCL blend provided an optimal balance of mechanical properties, thermal stability, and biodegradability.

[0167] In the molding stage, conditions of mold temperature 130-150℃, injection pressure 8-15MPa, and cooling time 30-45 seconds, along with appropriate post-treatment, were identified as key factors in improving the surface quality, dimensional stability, impact resistance, and moisture resistance of the product.

[0168] The chitosan-based biodegradable plastic produced through this stepwise optimization possesses excellent physical properties (tensile strength 35-48 MPa, elongation 150-210%, heat distortion temperature 95-108℃) and biodegradability (more than 90% decomposition within 180 days) that can replace existing petroleum-based plastics. In particular, the present invention is evaluated as an eco-friendly technology that can contribute to resource recycling and environmental protection by converting shrimp shell byproducts, which are fisheries waste, into high-value-added materials.

[0169] Example regarding changes in physical properties of a chitosan complex according to zennipin concentration division Amount of Jennipin added (parts by weight) Tensile strength (MPa) Growth rate (%) Heat distortion temperature (°C) Water absorption rate (%) Biodegradation rate (%, 180 days) Example 16 0.4 33.2 157 93.8 16.5 95.8 Example 10 0.5 35.8 152 95.3 15.2 95.3 Example 17 0.8 38.7 142 98.2 13.8 93.5 Example 11 1.0 42.5 185 102.7 12.5 92.8 Example 18 1.3 45.8 193 105.4 11.2 91.2 Example 12 1.5 48.3 210 108.5 10.3 90.2 Example 19 1.6 49.2 185 109.3 9.8 87.4 Comparative Example 10 0.3 28.2 125 88.5 18.7 97.5 Comparative Example 11 2.0 50.5 105 112.3 8.5 65.3

[0170] Examples 16-19 are experimental results obtained by further subdividing the amount of gennipin added within the scope of the claims. It was confirmed that excellent physical properties and a biodegradability of approximately 90% were observed in the range of 0.4 to 1.6 parts by weight of gennipin added. Of particular note is that when comparing gennipin concentrations of 1.5 parts by weight and 1.6 parts by weight, at 1.6 parts by weight, the elongation rate decreases sharply from 210% to 185%, and the biodegradability rate begins to decline from 90.2% to 87.4%. Additionally, when comparing gennipin concentrations of 0.4 parts by weight and 0.5 parts by weight, 0.4 parts by weight still exhibit a tensile strength of 33.2 MPa and a water absorption rate of 16.5%, but at 0.5 parts by weight, the tensile strength increases to 35.8 MPa and the water absorption rate decreases to 15.2%, indicating a significant improvement in physical properties.

[0171] These results clearly demonstrate that the range of 0.5 to 1.5 parts by weight of gennipin added as presented in the claim is the optimal range of critical significance. In particular, it was experimentally proven that the balance between physical properties and biodegradability begins to break down starting from 1.6 parts by weight, which slightly exceeds the upper limit of 1.5 parts by weight, and that below the lower limit of 0.5 parts by weight, the cross-linking effect is insufficient, thereby limiting the improvement of physical properties.

[0172] Example regarding changes in physical properties of a chitosan complex according to graphene oxide concentration division Amount of graphene oxide added (parts by weight) Tensile strength (MPa) Heat distortion temperature (°C) transparency(%) Electrical conductivity (S / cm) Biodegradation rate (%, 180 days) Example 20 0.25 32.5 93.2 83.8 1.2×10^-8 96.2 Example 10 0.3 35.8 95.3 82.5 2.5×10^-8 95.3 Example 21 0.4 38.3 98.7 80.2 5.8×10^-8 94.1 Example 11 0.5 42.5 102.7 78.3 8.3×10^-8 92.8 Example 22 0.6 45.7 105.2 76.5 1.2×10^-7 91.5 Example 12 0.7 48.3 108.5 75.1 2.5×10^-7 90.2 Example 23 0.75 49.5 109.8 73.2 5.8×10^-7 85.3 Comparative Example 10 0.2 28.2 88.5 85.2 5.5×10^-9 97.5 Comparative Example 11 1.0 50.5 112.3 68.7 1.2×10^-6 65.3

[0173] Examples 20-23 are experimental results in which the amount of graphene oxide added was further subdivided within and outside the claimed range. It is noteworthy that while the tensile strength and heat distortion temperature gradually increase in the range of 0.25-0.75 parts by weight of graphene oxide added, the biodegradability decreases sharply from 90.2% to 85.3% when comparing 0.7 parts by weight of graphene oxide with 0.75 parts by weight of graphene oxide.

[0174] This clearly demonstrates that 0.7 parts by weight of graphene oxide added is the upper limit that provides the optimal balance point for maintaining biodegradability and improving physical properties. In addition, when comparing 0.25 parts by weight and 0.3 parts by weight of graphene oxide, the tensile strength improved significantly from 32.5 MPa to 35.8 MPa starting from 0.3 parts by weight, proving the critical significance of 0.3 parts by weight, which is the lower limit presented in the claim.

[0175] Additionally, an improvement in electrical conductivity was confirmed with increasing graphene oxide content, suggesting the potential for graphene oxide-based composites to be utilized as functional biodegradable plastics with antistatic and electromagnetic shielding capabilities.

[0176] Examples regarding chitosan manufacturing characteristics according to microwave treatment conditions division Microwave output (W) Processing cycle Ascorbic acid (parts by weight) Degree of deacetylation (%) Molecular weight (kDa) Process time (minutes) Energy consumption (kWh / kg) Example 24 550 5 0.5 81.8 225 85 0.53 Example 7 600 6 0.5 85.3 220 78 0.55 Example 25 650 6 1.0 87.2 210 76 0.58 Example 8 700 7 1.0 88.7 195 74 0.60 Example 26 750 7 1.0 90.1 185 72 0.62 Example 9 800 8 1.5 91.5 175 70 0.65 Example 27 850 8 1.5 92.2 155 68 0.70 Comparative Example 7 500 5 0.3 78.2 235 82 0.50 Comparative Example 8 900 9 2.0 93.2 120 68 0.75 Comparative Example 9 - (Hydrothermal treatment) - - 86.5 130 480 1.00

[0177] Examples 24-27 are experimental results in which microwave output and processing cycles were applied with further subdivisions within and outside the scope of the claims. Under the condition of a microwave output of 550 W and 5 processing cycles (Example 24), the degree of deacetylation was 81.8%, which did not meet the 85% or higher requirement specified in the claims. On the other hand, under the condition of a microwave output of 850 W and 8 processing cycles (Example 27), the molecular weight was 155 kDa, which is lower than the 175 kDa or higher requirement specified in the claims.

[0178] These results clearly demonstrate that a microwave power range of 600-800 W and 6-8 processing cycles is the critical range for simultaneously achieving a deacetylation degree of over 85% and a molecular weight of over 175 kDa. Furthermore, under the same processing cycle conditions, a trend was observed in which the deacetylation degree increased by approximately 1.5% and the molecular weight decreased by approximately 10 kDa for every 50 W increase in microwave power, confirming that precise control of power and processing cycles has a significant impact on the quality of the final product.

[0179] Examples regarding chitin extraction characteristics according to enzyme complex composition and content division Protease:lipase ratio Amount of enzyme complex added (parts by weight) Protein removal rate (%) Lipid removal rate (%) Chitin purity (%) Chitin Yield (%) pH stability Example 28 2:1 2.0 95.8 92.3 91.2 88.5 middle Example 4 1:1 2.0 94.3 93.8 92.5 87.3 excellence Example 29 1:2 2.0 92.5 95.2 91.8 86.2 excellence Example 30 1:1 3.0 95.8 94.7 93.7 86.5 excellence Example 5 1:1 3.5 96.7 95.3 94.8 85.7 excellence Example 31 1:1 4.0 97.3 96.1 95.2 84.8 excellence Example 6 1:1 5.0 97.9 96.8 96.2 83.5 excellence Example 32 1:1 5.5 98.2 97.3 96.5 81.2 middle Comparative Example 4 1:1 1.0 88.5 87.2 88.7 89.2 low Comparative Example 5 1:1 6.0 98.4 97.8 96.5 78.3 low Comparative Example 6 - - 95.2 92.5 94.5 70.2 -

[0180] Examples 28-32 are experimental results in which the composition and amount of the enzyme complex were applied with further refinement within and outside the scope of the claims. When analyzing the results according to changes in the ratio of protease to lipase (Examples 28, 4, and 29), the balance between protein removal rate and lipid removal rate was best at a 1:1 ratio (Example 4), maximizing chitin purity to 92.5%. This suggests that a 1:1 enzyme ratio is optimal when considering the ratio of protein to lipid contained in shrimp shells.

[0181] When analyzing the results based on the amount of enzyme complex added, in the range of 2.0 to 5.0 parts by weight (Examples 4, 30, 5, 31, 6), chitin purity gradually improved with increasing addition amount, whereas when comparing 5.0 parts by weight (Example 6) and 5.5 parts by weight (Example 32), the chitin yield began to decrease rapidly from 83.5% to 81.2%. In addition, it was confirmed that pH stability also began to decline starting from 5.5 parts by weight, which could have a negative impact on the quality of the final product.

[0182] These results clearly demonstrate that the range of 2.0 to 5.0 parts by weight of the enzyme complex added is a critical range that provides an optimal balance between chitin purity and yield. In particular, the yield decreases sharply and pH stability deteriorates starting from 5.5 parts by weight, which slightly exceeds the upper limit of 5.0 parts by weight, thus experimentally proving the critical significance of the upper limit presented in the claim.

[0183] Example regarding changes in physical properties of biodegradable plastics due to the addition of epoxidized soybean oil division Amount of epoxidized soybean oil added (parts by weight) Growth rate (%) Impact strength (J / m) Flexibility (Shore D) Ease of processing Biodegradation rate (%, 180 days) Example 33 12 135 28.5 78 commonly 96.8 Example 34 14 148 30.2 75 Good 96.2 Example 10 15 152 32.5 73 Good 95.3 Example 35 18 170 35.8 70 excellence 93.7 Example 11 20 185 38.3 68 excellence 92.8 Example 36 23 195 40.5 65 eminence 91.5 Example 12 25 210 42.8 63 eminence 90.2 Example 37 27 215 43.2 60 eminence 85.5 Comparative Example 10 10 125 25.3 82 error 97.5 Comparative Example 11 30 220 44.5 58 eminence 78.3

[0184] Examples 33-37 are experimental results in which the amount of epoxidized soybean oil added was further subdivided within and outside the claimed range. It was confirmed that the elongation rate and impact strength gradually increased in the range of 12-27 parts by weight of epoxidized soybean oil added. It is noteworthy that when comparing 25 parts by weight of epoxidized soybean oil (Example 12) and 27 parts by weight (Example 37), the elongation rate increased slightly from 210% to 215%, while the biodegradability rate decreased sharply from 90.2% to 85.5%.

[0185] In addition, when comparing 14 parts by weight (Example 34) and 15 parts by weight (Example 10) of epoxidized soybean oil, the ease of processing was significantly improved at 15 parts by weight, confirming the critical significance of 15 parts by weight, which is the lower limit presented in the claim. These results clearly demonstrate that the range of 15-25 parts by weight of epoxidized soybean oil addition is a critical range that provides an optimal balance point for elongation, impact strength, processability, and biodegradability.

[0186] Examples regarding changes in physical properties according to the composition and content of a biodegradable auxiliary polymer blend division Starch:PCL ratio Blend addition amount (parts by weight) Tensile strength (MPa) Melt flow index (g / 10min) Biodegradation rate (%, 90 days) Biodegradation rate (%, 180 days) Example 38 1:1 35 38.5 5.8 52.3 88.5 Example 39 1:2 35 42.5 8.2 48.7 92.8 Example 40 1:3 35 45.8 10.5 42.5 85.3 Example 41 2:1 35 35.2 4.3 58.5 95.2 Example 42 1:2 28 47.2 6.5 45.2 89.5 Example 10 1:2 30 45.5 7.3 47.5 95.3 Example 11 1:2 35 42.5 8.2 48.7 92.8 Example 12 1:2 40 38.7 9.5 50.2 90.2 Example 43 1:2 42 36.3 10.2 50.8 88.5 Comparative Example 10 1:2 25 48.5 5.2 43.5 87.2 Comparative Example 11 1:2 45 33.5 12.3 52.5 85.5

[0187] Examples 38-43 are experimental results in which the composition and addition amount of the biodegradable auxiliary polymer blend were further subdivided within and outside the scope of the claims. When analyzing the results according to changes in the ratio of starch to PCL (Examples 38-41), it was confirmed that the balance between tensile strength and biodegradability was best at a 1:2 ratio (Example 39). At a 1:1 ratio (Example 38), the biodegradability was high but the tensile strength and melt flow index decreased, and at a 1:3 ratio (Example 40), the tensile strength and melt flow index improved but the biodegradability decreased significantly.

[0188] When analyzing the results according to the amount of blend added, in the range of 30-40 parts by weight (Examples 10-12), the tensile strength gradually decreased, while the melt flow index and biodegradability (90 days) showed an increasing trend. It is noteworthy that when comparing the blend addition amounts of 40 parts by weight (Example 12) and 42 parts by weight (Example 43), the tensile strength decreased sharply from 38.7 MPa to 36.3 MPa, and the biodegradability (180 days) also decreased from 90.2% to 88.5%.

[0189] In addition, when comparing the blend addition amounts of 28 parts by weight (Example 42) and 30 parts by weight (Example 10), the melt flow index at 30 parts by weight increased significantly from 6.5 g / 10 min to 7.3 g / 10 min, improving processability, and the biodegradability rate (180 days) was also optimized from 89.5% to 95.3%. These results clearly demonstrate that the range of 30-40 parts by weight of the biodegradable auxiliary polymer blend addition amount presented in the claims is a critical range that provides an optimal balance point for mechanical properties, processability, and biodegradability.

[0190] conclusion

[0191] As a result of the analysis of additional embodiments of the present invention, it was clearly demonstrated that the content ranges of each component and process conditions described in the claims are critical ranges that optimize the quality and performance of the product. In particular, numerical ranges such as the amount of gennipin added (0.5-1.5 parts by weight), the amount of graphene oxide added (0.3-0.7 parts by weight), microwave treatment conditions (600-800W, 6-8 cycles), the amount of enzyme complex added (2-5 parts by weight), the amount of epoxidized soybean oil added (15-25 parts by weight), and the amount of biodegradable auxiliary polymer blend added (30-40 parts by weight) were found to exhibit critical characteristics in which physical properties or process efficiency change rapidly at their respective boundary values.

[0192] By comparing results inside and outside the claimed range through detailed experiments near the lower and upper limits of each range, it was objectively proven that the claimed numerical range is a critical range that provides substantial and unexpected technical effects, rather than a simple design change. Therefore, the contents and effects described in the claims of the present invention are sufficiently supported by the examples and comparative examples, presenting clear experimental grounds to prove the inventive step of the invention.

[0193] Results and Discussion

[0194] 1. Optimization of the pretreatment process for shrimp shell by-products

[0195] In this study, a pretreatment process was optimized to extract high-quality chitin from shrimp shell byproducts. According to the experimental results presented in Tables 1 and 2, conditions of a sodium chloride concentration of 0.5-1.5 parts by weight, an ultrasonic frequency of 20-40 kHz, and a treatment time of 15-25 minutes were found to provide an optimal balance between impurity removal efficiency and the preservation of the molecular structure of chitin.

[0196] As a result of the analysis of Examples 1-3, as the sodium chloride concentration increased from 0.5 parts by weight to 1.5 parts by weight, the impurity removal rate improved from 92.5% to 97.2%, and the chitin purity also increased from 91.8% to 94.7%. Notably, in Example 2 (1.0 parts by weight sodium chloride, 30 kHz ultrasound, 20 minutes), an optimal balance was achieved between the impurity removal rate (95.8%) and the processing time (13 hours). This suggests that an intermediate salt concentration and ultrasonic treatment conditions are optimal conditions for efficient pretreatment.

[0197] On the other hand, in Comparative Example 1, the sodium chloride concentration (0.3 parts by weight) and the ultrasonic treatment conditions (10 kHz, 10 minutes) were both set below the lower limit of the claimed range, resulting in an impurity removal rate of only 85.3%. This is because the ionic strength was insufficient, which prevented the effective removal of impurities and microorganisms from the surface of the shrimp shells. As a result of molecular structure analysis, it was confirmed that proteins and minerals remained in the chitin structure due to insufficient pretreatment, thereby reducing the efficiency of subsequent processes.

[0198] In Comparative Example 2, both the sodium chloride concentration (2.0 parts by weight) and the ultrasonic treatment conditions (50 kHz, 30 min) were applied in excess of the upper limit of the claims. The impurity removal rate (97.5%) was similar to that of Example 3 (97.2%), but gel permeation chromatography (GPC) analysis confirmed that the number-average molecular weight of chitin decreased by approximately 15% compared to Example 3. This is interpreted as being due to the excessive salt concentration and ultrasonic energy partially cleaving the glycosidic bonds of the chitin molecules. Since a decrease in molecular weight can be a major cause of the degradation of the mechanical properties of the final biodegradable plastic, precise control of the pretreatment conditions is important.

[0199] Additionally, in Comparative Example 3, a conventional stirring method (60 minutes) was applied instead of ultrasonic treatment. As a result, the process time increased significantly to 23 hours, and the impurity removal rate was 93.1%, which was lower than that of the example. In particular, a problem occurred where the final product turned yellow, which was analyzed to be caused by partial deacetylation and oxidation reactions of chitin due to the use of high-concentration sodium hydroxide. These results demonstrate that the introduction of ultrasonic technology plays a key role in improving process efficiency and product quality.

[0200] Field emission scanning electron microscope (FE-SEM) observations showed that the shrimp shells treated under the conditions of Examples 1-3 had clean surfaces and well-preserved micropore structures, whereas impurities remained on the surface in Comparative Example 1 and surface damage was observed in Comparative Example 2. This demonstrates at a microscopic level that optimal pretreatment conditions provide a balance between impurity removal and the preservation of the chitin structure.

[0201] In conclusion, pretreatment conditions of a sodium chloride concentration of 0.5-1.5 parts by weight, an ultrasonic frequency of 20-40 kHz, and a treatment time of 15-25 minutes have technical importance as optimal conditions for extracting high-quality chitin from shrimp shell by-products.

[0202] 2. Streamlining the Chitin Extraction Process Using Enzymatic Methods

[0203] According to the experimental results presented in Tables 3, 4, and 14, conditions of hydrochloric acid concentration of 1.8-2.2 parts by weight, ethanol:acetone ratio of 3:2, and enzyme complex addition amount of 2-5 parts by weight were found to optimize the purity and yield of chitin.

[0204] Analysis of the results of Examples 4-6 showed that as the hydrochloric acid concentration increased from 1.8 parts by weight to 2.2 parts by weight, the calcium carbonate removal rate improved from 96.3% to 99.2%, and the chitin purity also increased from 92.5% to 96.2%. X-ray diffraction (XRD) analysis confirmed that the crystal structure of chitin was well preserved under all conditions of Examples 4-6, and that the diffraction peaks corresponding to calcium carbonate were effectively removed.

[0205] The results of Examples 28-32, performed to analyze the effect of the enzyme complex in more detail, show that the composition and amount of the enzyme complex have a decisive influence on chitin extraction efficiency. When analyzing the results according to changes in the ratio of protease to lipase (Examples 28, 4, and 29), the balance between the protein removal rate (94.3%) and the lipid removal rate (93.8%) was best at a 1:1 ratio (Example 4), maximizing chitin purity to 92.5%. This means that a 1:1 enzyme ratio is optimal when considering the ratio of protein to lipid contained in shrimp shells.

[0206] When examining the changes according to the amount of enzyme complex added, in the range of 2.0 to 5.0 parts by weight (Examples 4, 30, 5, 31, 6), chitin purity gradually improved from 92.5% to 96.2% as the amount added increased, while chitin yield decreased gradually from 87.3% to 83.5%. Of particular note is that when comparing the amount of enzyme complex added at 5.0 parts by weight (Example 6) and 5.5 parts by weight (Example 32), the chitin yield began to decrease sharply from 83.5% to 81.2%. In addition, pH stability analysis results confirmed that when more than 5.5 parts by weight of enzyme were added, the pH fluctuation of the reaction solution increased, causing precipitation of protein degradation products and negatively affecting chitin purity and yield.

[0207] In Comparative Example 4, the hydrochloric acid concentration (1.5 parts by weight), the amount of enzyme added (1.0 parts by weight), etc., were set below the lower limit of the claimed range. As a result, the calcium carbonate removal rate was only 91.5%, and the chitin purity decreased to 88.7%. As a result of Fourier Transistor (FTIR) analysis, a characteristic peak of calcium carbonate around 1420 cm⁻¹ was still observed, confirming that demineralization proceeded incompletely. In addition, through the analysis of the intensity ratio of the amide I and amide II bands, it was quantitatively verified that the protein removal rate was low at 88.5%.

[0208] In Comparative Example 5, the hydrochloric acid concentration (2.5 parts by weight) and the amount of enzyme added (6.0 parts by weight) were applied in excess of the upper limit of the claims. The chitin purity (96.5%) was similar to that of Example 6 (96.2%), but the chitin yield decreased significantly to 78.3%. Molecular weight analysis confirmed that the molecular weight decreased by approximately 20% due to partial hydrolysis of chitin caused by the excessive acid concentration. In addition, the partial decomposition of the chitin itself due to the excessive addition of enzyme also contributed to the decrease in yield.

[0209] In Comparative Example 6, a conventional chemical method (5.0 parts by weight hydrochloric acid, strong alkaline conditions of pH 11.0) was applied instead of an enzymatic method. As a result, the chitin purity (94.5%) was similar to that of Example 5 (94.8%), but the chitin yield decreased significantly to 70.2%. Energy consumption also increased by 30-40% compared to the example, which was found to be disadvantageous in terms of process efficiency. In particular, scanning electron microscopy observations revealed that the strong alkaline treatment damaged the microfiber structure of the chitin, which could reduce the efficiency of the subsequent deacetylation process.

[0210] The effect of the mixing ratio of ethanol and acetone (3:2) is also noteworthy. As a result of the analysis of pigment removal rates, the removal efficiency of carotenoid pigments was optimized to over 95% at a 3:2 ratio. This is interpreted as being due to the complementary interaction between the polarity of ethanol and the non-polarity of acetone, which effectively dissolved pigment components with various polarities. Furthermore, as a result of the analysis of solvent recovery rates, it was confirmed that the 3:2 ratio is also advantageous in terms of economic efficiency.

[0211] In conclusion, conditions of a hydrochloric acid concentration of 1.8-2.2 parts by weight, an ethanol:acetone ratio of 3:2, and an enzyme complex addition amount of 2-5 parts by weight are technically important as critical conditions for optimizing the purity, yield, and economic feasibility of chitin extraction. In particular, the introduction of enzymatic methods has been confirmed to have a significant advantage over existing chemical methods in terms of reducing environmental burden and preserving chitin structure.

[0212] 3. Analysis of the Effects of Microwave-Assisted Deacetylation Technology

[0213] According to the experimental results presented in Tables 5, 6, and 13, conditions of a sodium hydroxide concentration of 35-45 parts by weight, an ascorbic acid addition amount of 0.5-1.5 parts by weight, a microwave power of 600-800 W, and 6-8 treatment cycles were found to optimize the degree of deacetylation and molecular weight of chitosan.

[0214] Analysis of the results of Examples 7-9 shows that as the sodium hydroxide concentration increased from 35 parts by weight to 45 parts by weight, the degree of deacetylation increased from 85.3% to 91.5%, while the molecular weight of chitosan showed a tendency to decrease from 220 kDa to 175 kDa. This is interpreted as being due to the fact that as the strong alkali concentration increases, the efficiency of removing acetyl groups from chitin improves, while the hydrolysis of glycosidic bonds is also promoted. The degree of deacetylation measured by nuclear magnetic resonance (1H-NMR) spectrum analysis increased in proportion to the sodium hydroxide concentration, while the molecular weight measured by GPC analysis showed a clear tendency to decrease in inverse proportion.

[0215] The results of Examples 24-27, performed to analyze the effects of microwave treatment conditions in more detail, show that microwave power and the number of treatment cycles have a decisive influence on the deacetylation process. As the microwave power increased from 550 W (Example 24) to 850 W (Example 27), the degree of deacetylation increased from 81.8% to 92.2%, while the molecular weight of chitosan decreased from 225 kDa to 155 kDa. Of particular note is that under the condition of a microwave power of 550 W and 5 treatment cycles (Example 24), the degree of deacetylation was 81.8%, which did not meet the 85% or higher requirement of the claim, and under the condition of a microwave power of 850 W and 8 treatment cycles (Example 27), the molecular weight was 155 kDa, which was lower than the 175 kDa or higher requirement of the claim.

[0216] These results clearly demonstrate that a microwave power of 600-800 W and 6-8 processing cycles constitute the critical range capable of simultaneously achieving a deacetylation degree of over 85% and a molecular weight of over 175 kDa. Thermal imaging analysis confirmed that the temperature distribution within the reaction solution remained uniform during the microwave processing, preventing localized overheating and minimizing damage to the molecular structure of chitosan. In particular, by setting a periodic resting time (2 minutes), a uniform heat distribution was induced, and the reduction in molecular weight could be effectively suppressed.

[0217] The effect of adding ascorbic acid is clearly demonstrated through a comparison between Examples 7-9 and Comparative Example 9 (without addition). In Examples 7-9, 0.5-1.5 parts by weight of ascorbic acid were added, maintaining the molecular weight of chitosan at 175-220 kDa, whereas in Comparative Example 9, the molecular weight decreased to 130 kDa due to the absence of ascorbic acid. Electron spin resonance (ESR) analysis confirmed that ascorbic acid effectively removes free radicals generated during the deacetylation process, thereby inhibiting the oxidative degradation of chitosan. In particular, within the range of 0.5-1.5 parts by weight of added ascorbic acid, the balance between radical scavenging activity and the deacetylation reaction was optimized.

[0218] In Comparative Example 7, the sodium hydroxide concentration (30 parts by weight), the amount of ascorbic acid added (0.3 parts by weight), and the microwave power (500 W) were set below the lower limit of the claimed range. As a result, the degree of deacetylation was low at 78.2%, which reduced the solubility and reactivity of the final chitosan. FTIR analysis confirmed that the amide I band at 1655 cm⁻¹ and the amide III band at 1320 cm⁻¹ were still strongly observed, indicating that deacetylation proceeded incompletely.

[0219] In Comparative Example 8, the sodium hydroxide concentration (50 parts by weight), the amount of ascorbic acid added (2.0 parts by weight), and the microwave output (900 W) were applied in excess of the upper limit of the claimed scope. Although the degree of deacetylation (93.2%) was excellent, the molecular weight of chitosan decreased significantly to 120 kDa. It was analyzed that the glycosidic bonds of chitosan were hydrolyzed and the molecular chains were cleaved due to the excessive sodium hydroxide concentration and microwave energy. Furthermore, it was confirmed that an excess amount of ascorbic acid could act as a pro-oxidant and promote the oxidative decomposition of chitosan.

[0220] In Comparative Example 9, the conventional hydrothermal treatment method (8 hours) was applied instead of microwave treatment. As a result, the process time increased to 480 minutes, which is about 6-7 times compared to microwave treatment (70-78 minutes), and energy consumption also increased by 35-45%. The degree of deacetylation (86.5%) was similar to Example 7 (85.3%), but the molecular weight of chitosan decreased to 130 kDa, which is about 40% lower than Example 7 (220 kDa). It is interpreted that continuous heat exposure due to long-term hydrothermal treatment promoted damage to the molecular structure of chitosan.

[0221] In conclusion, conditions of a sodium hydroxide concentration of 35-45 parts by weight, an ascorbic acid addition amount of 0.5-1.5 parts by weight, a microwave power of 600-800 W, and 6-8 processing cycles are of technical importance as critical conditions for optimizing the degree of deacetylation and molecular weight of chitosan. In particular, the combination of microwave-assisted deacetylation technology and the addition of antioxidants is evaluated as an innovative approach that can simultaneously achieve reduced process time and the production of high-quality chitosan.

[0222] 4. Enhancement of Chitosan Properties through Biological Crosslinking and Nanocompositing

[0223] According to the experimental results presented in Tables 7, 8, 11, and 12, it was confirmed that the conditions of adding 0.5-1.5 parts by weight of zennipin, 0.3-0.7 parts by weight of graphene oxide, 15-25 parts by weight of epoxidized soybean oil, and 30-40 parts by weight of starch:PCL blend optimize the physical properties of chitosan-based biodegradable plastics.

[0224] First, the results of Examples 10-12 and 16-19, performed to analyze the effect of the amount of zennipin added, show that biological crosslinking through zennipin has a decisive influence on the physical properties of the chitosan complex. As the amount of zennipin added increased from 0.4 parts by weight (Example 16) to 1.6 parts by weight (Example 19), the tensile strength increased from 33.2 MPa to 49.2 MPa, and the water absorption rate decreased from 16.5% to 9.8%. Of particular note is that when comparing the zennipin concentrations of 0.4 parts by weight and 0.5 parts by weight, starting from 0.5 parts by weight, the tensile strength increased sharply from 33.2 MPa to 35.8 MPa, and the water absorption rate decreased significantly from 16.5% to 15.2%.

[0225] In addition, when comparing the gennipin concentrations of 1.5 parts by weight (Example 12) and 1.6 parts by weight (Example 19), the elongation rate decreased sharply from 210% to 185%, and the biodegradability rate began to decline from 90.2% to 87.4%. This is interpreted as being due to the reduced flexibility of the chitosan molecular chains and decreased accessibility of the enzyme caused by excessive cross-linking. As a result of FTIR analysis, the peak intensity at 1655 cm⁻¹ (C=N stretching vibration) increased with increasing gennipin addition, confirming the progress of cross-linking, and it was analyzed that at 1.6 parts by weight or higher, almost all of the amino groups of chitosan reacted and reached a saturation state.

[0226] The results of Examples 10-12 and 20-23, performed to analyze the effect of graphene oxide addition amount, show that nanocompositing with graphene oxide significantly improves the mechanical properties and thermal stability of the chitosan composite. As the graphene oxide addition amount increased from 0.25 parts by weight (Example 20) to 0.75 parts by weight (Example 23), the tensile strength increased from 32.5 MPa to 49.5 MPa, and the heat distortion temperature rose from 93.2°C to 109.8°C. It is noteworthy that when comparing 0.25 parts by weight and 0.3 parts by weight of graphene oxide, the tensile strength improved significantly from 32.5 MPa to 35.8 MPa starting from 0.3 parts by weight, proving the critical significance of 0.3 parts by weight, which is the lower limit specified in the claim.

[0227] In addition, when comparing 0.7 parts by weight of graphene oxide (Example 12) and 0.75 parts by weight (Example 23), the biodegradation rate decreased sharply from 90.2% to 85.3%. This is analyzed to be due to the excessive addition of graphene oxide restricting access by biodegradation enzymes and inhibiting the metabolic activity of microorganisms. Transmission electron microscopy (TEM) observations showed that up to 0.7 parts by weight, the graphene oxide was uniformly dispersed in the chitosan matrix, whereas at 0.75 parts by weight or more, partial aggregation was observed. Such aggregation can lead to structural non-uniformity of the composite, which may limit the effect of improving physical properties.

[0228] Additionally, as a result of analyzing the change in electrical conductivity due to the addition of graphene oxide, the electrical conductivity increased approximately 100-fold from 5.5×10^-9 S / cm (Comparative Example 10) to 5.8×10^-7 S / cm (Example 23) as the amount of addition increased. This is attributed to the formation of a conductive network of graphene oxide and suggests the possibility of application as a functional biodegradable plastic with antistatic and electromagnetic shielding functions.

[0229] The results of Examples 10-12 and 33-37, performed to analyze the effect of epoxidized soybean oil, show that epoxidized soybean oil has a decisive influence on the flexibility and processability of the chitosan complex. As the amount of epoxidized soybean oil added increased from 12 parts by weight (Example 33) to 27 parts by weight (Example 37), the elongation increased significantly from 135% to 215%, and the impact strength also improved from 28.5 J / m to 43.2 J / m. Of particular note is that when comparing 14 parts by weight (Example 34) and 15 parts by weight (Example 10) of epoxidized soybean oil, the ease of processing improved significantly from good to excellent starting from 15 parts by weight.

[0230] As a result of the Melt Flow Index (MFI) analysis, it was confirmed that when the amount of epoxidized soybean oil added was 15 parts by weight or more, the MFI value was maintained above the reference value (5.0 g / 10 min), allowing for smooth thermoplastic processing. This is interpreted to be because the epoxidized soybean oil is inserted between the chitosan molecular chains, weakening intermolecular interactions and increasing chain mobility. The glass transition temperature (Tg) measured by dynamic mechanical analysis (DMA) also decreased with increasing amount of epoxidized soybean oil, objectively proving the plasticizing effect.

[0231] In addition, when comparing 25 parts by weight (Example 12) and 27 parts by weight (Example 37) of epoxidized soybean oil, the elongation rate increased slightly from 210% to 215%, while the biodegradability rate decreased sharply from 90.2% to 85.5%. This is analyzed to be due to the excessive addition of plasticizer causing phase separation between chitosan and the plasticizer, and the increased hydrophobicity, which reduces the accessibility of biodegradation enzymes. Scanning electron microscopy observations revealed that at 27 parts by weight or more, fine plasticizer droplets were observed on the surface, confirming the phase separation phenomenon.

[0232] The results of Examples 10-12 and 38-43, performed to analyze the effect of biodegradable auxiliary polymer blends, show that the composition and amount of starch and PCL have a complex effect on the physical properties and biodegradability of the final biodegradable plastic. When analyzing the results according to changes in the ratio of starch to PCL (Examples 38-41), it was confirmed that the balance between tensile strength (42.5 MPa) and biodegradability (92.8%) was best at a 1:2 ratio (Example 39). At a 1:1 ratio (Example 38), the biodegradability was high but the tensile strength and melt flow index decreased, and at a 1:3 ratio (Example 40), the tensile strength and melt flow index improved but the biodegradability decreased significantly.

[0233] When analyzing the results according to the amount of blend added, in the range of 30-40 parts by weight (Examples 10-12), the tensile strength gradually decreased from 45.5 MPa to 38.7 MPa as the amount added increased, while the melt flow index increased from 7.3 g / 10 min to 9.5 g / 10 min. Of particular note is that when comparing the blend addition amounts of 28 parts by weight (Example 42) and 30 parts by weight (Example 10), the melt flow index increased significantly from 6.5 g / 10 min to 7.3 g / 10 min starting from 30 parts by weight, improving processability, and the biodegradability (180 days) was also optimized from 89.5% to 95.3%.

[0234] In addition, when comparing blend addition amounts of 40 parts by weight (Example 12) and 42 parts by weight (Example 43), the tensile strength decreased sharply from 38.7 MPa to 36.3 MPa, and the biodegradation rate (180 days) also decreased from 90.2% to 88.5%. This is interpreted as being due to the excessive addition of blend disrupting the continuity of the chitosan matrix and causing phase separation. As a result of X-ray diffraction analysis, at 42 parts by weight or more, the crystal peaks of chitosan and PCL were clearly separated, allowing for objective confirmation of the phase separation phenomenon.

[0235] The results of Comparative Examples 10, 11, and 12 clearly demonstrate the problems that occur under conditions outside the scope of the claims. In Comparative Example 10, the amount of each additive was set below the lower limit of the claims, so although the tensile strength (28.2 MPa) was relatively high, the elongation (125%) and heat distortion temperature (88.5℃) were low, resulting in an overall deterioration of physical properties. In particular, the ease of processing was evaluated as poor, and it was analyzed that there would be limitations on actual industrial application.

[0236] In Comparative Example 11, the amount of each additive was applied in excess of the upper limit of the claim scope. Although the tensile strength (50.5 MPa) and heat distortion temperature (112.3℃) were high, the elongation decreased to 105% and the biodegradability decreased significantly to 65.3%, compromising the core characteristics as a biodegradable plastic. In addition, the transparency also decreased to 68.7%, confirming a problem of poor visual quality.

[0237] In Comparative Example 12, zennipin and graphene oxide were not added, and other conditions were applied identically to Example 11. As a result, the tensile strength decreased significantly to 25.3 MPa and the water absorption rate increased to 28.5%, resulting in a significant decrease in water resistance. This demonstrates that cross-linking through zennipin and graphene oxide nano-filling are essential elements for improving the physical properties of the chitosan composite.

[0238] In conclusion, the conditions of adding 0.5-1.5 parts by weight of zennipin, 0.3-0.7 parts by weight of graphene oxide, 15-25 parts by weight of epoxidized soybean oil, and 30-40 parts by weight of starch:PCL blend are of technical importance as critical conditions for optimizing the mechanical properties, thermal stability, processability, and biodegradability of chitosan-based biodegradable plastics. In particular, it has been confirmed that comprehensive property improvements, which are difficult to achieve with a single material, can be realized through the synergistic effects of these components.

[0239] 5. Optimization of the biodegradable plastic molding process

[0240] According to the experimental results presented in Tables 9 and 10, it was confirmed that an appropriate post-treatment method, along with conditions of mold temperature 130-150℃, injection pressure 8-15MPa, and cooling time 30-45 seconds, optimizes the quality of biodegradable plastic products.

[0241] Analyzing the results of Examples 13-15, it was confirmed that when various molding methods (injection, compression, blow) were applied, products with excellent surface quality (4.3-4.8 points), dimensional stability (97.5-99.1%), and impact resistance (45.2-52.3 J / m) were manufactured. In particular, Example 14 (compression molding, UV surface treatment) showed the best surface quality (4.8 points) and surface moisture resistance (92.3°). This is interpreted as being due to the effective removal of internal bubbles through uniform pressure distribution during the compression molding process and the increased cross-linking density on the surface through UV surface treatment.

[0242] Analyzing the effects of molding conditions, it was confirmed that mold temperature is a key factor determining the quality of the molded product. In Comparative Example 13, the mold temperature was applied at 110°C, which is less than 130°C, resulting in reduced fluidity of the molten material and incomplete filling, leading to a low surface quality score of 3.2 and a decrease in product yield to 90.3%. Thermal imaging analysis revealed that at 110°C, a significant temperature gradient formed between the mold surface and the interior, causing shrinkage and deformation during the cooling process.

[0243] On the other hand, in Comparative Example 14, the mold temperature was applied at 190°C, which exceeded 150°C, resulting in the thermal decomposition of chitosan and starch. As a result of thermogravimetric analysis (TGA), rapid thermal decomposition of chitosan and starch proceeded at temperatures above 180°C, and weight loss was observed. Consequently, the product yield dropped significantly to 85.7%, and a problem of yellowing occurred. Through gas chromatography-mass spectrometry (GC-MS), low-molecular-weight amino sugar derivatives, which are thermal decomposition products, were detected in the specimen prepared at 190°C, objectively confirming the occurrence of thermal decomposition.

[0244] The influence of the post-treatment method is also noteworthy. Compared to Comparative Example 15 (extrusion molding, untreated), Examples 13-15 showed improved results in surface quality, dimensional stability, impact resistance, and surface moisture resistance due to the application of appropriate post-treatment. In particular, UV surface treatment (Example 14) significantly improved surface moisture resistance, increasing the contact angle to 92.3°. X-ray photoelectron spectroscopy (XPS) analysis confirmed that the surface chemical structure changed after UV treatment, with an increase in the oxygen / carbon ratio and the formation of new carbonyl groups. Through this surface modification, moisture absorption could be effectively suppressed.

[0245] In Comparative Example 15, surface quality (2.5 points), dimensional stability (92.5%), impact resistance (35.8 J / m), and surface moisture resistance (75.5°) were all degraded due to the application of the extrusion molding method and the failure to perform post-treatment. It was analyzed that the quality of the final product deteriorated because extrusion molding has limited shape control and low surface uniformity. In addition, fine cracks and pores were observed on the surface due to the failure to perform post-treatment, confirming that this could cause a deterioration of physical properties during long-term use.

[0246] In conclusion, appropriate post-treatment, along with molding conditions of a mold temperature of 130-150℃, injection pressure of 8-15MPa, and cooling time of 30-45 seconds, is of technical importance as a critical condition for optimizing the quality and performance of chitosan-based biodegradable plastic products. In particular, it has been proven that the surface quality, dimensional stability, impact resistance, and moisture resistance of the product can be comprehensively improved through an appropriate combination of molding methods and post-treatment methods.

[0247] 6. Comprehensive Performance Evaluation and Analysis of Application Potential

[0248] To evaluate the overall performance of the chitosan-based biodegradable plastic manufactured under the optimal conditions presented in this invention, a comparative analysis was performed with existing commercial biodegradable plastics and petroleum-based plastics. As a result, it was confirmed that the biodegradable plastic of this invention exhibits excellent balanced characteristics in various aspects, including mechanical properties, thermal stability, biodegradability, and economic feasibility.

[0249] In terms of tensile strength, the biodegradable plastic of the present invention (35-48 MPa) showed a value improved by approximately 100% compared to conventional chitosan-based plastics (15-25 MPa), and also showed a strength level of approximately 80% compared to commercial PLA (50-60 MPa). In particular, the low mechanical strength, which is a fundamental limitation of chitosan materials, was overcome due to the synergistic effect of biological crosslinking through gennipin and graphene oxide nanocomposite.

[0250] In terms of elongation, it exhibited excellent values ​​of 150-210% due to the plasticizing effect of epoxidized soybean oil, showing significantly higher flexibility than existing chitosan-based plastics (30-50%) and commercial PLA (2-6%). This effectively improves the brittleness that has been pointed out as a disadvantage of biodegradable plastics, and is a characteristic suitable for applications requiring flexibility, such as packaging materials and films.

[0251] In terms of thermal stability, the biodegradable plastic of the present invention exhibited a heat distortion temperature of 95-108°C, which was superior to that of conventional chitosan-based plastics (75-85°C). Thermogravimetric analysis results showed a 5% weight loss temperature (T5%) of approximately 290°C, objectively demonstrating excellent thermal stability. This improvement in thermal stability is due to the effects of crosslinking and nanocompositing, which expands the potential for use in thermal processing and high-temperature environments.

[0252] In terms of biodegradability, the biodegradable plastic of the present invention exhibited excellent biodegradability, degrading by more than 90% within 180 days. As a result of biodegradation tests under composting conditions (ISO 14855), the carbon conversion rate was confirmed to be more than 45% during the first 30 days and more than 90% after 180 days, demonstrating superior biodegradability compared to commercial biodegradable plastic PCL (80% after 180 days). In particular, it was proven that the rate of biodegradation can be effectively controlled by adding a starch and PCL blend.

[0253] In terms of moisture resistance, the combined effect of gennipin crosslinking, graphene oxide addition, and UV surface treatment limited the water absorption rate to 10-15%, showing a significantly improved result compared to existing chitosan-based plastics (30-40%). Contact angle measurements were also confirmed to be 85-92°, objectively proving excellent water resistance. This is considered a significant technological advancement that overcomes moisture sensitivity caused by the hydrophilicity of chitosan.

[0254] In terms of economic feasibility, the process of the present invention can reduce production costs by utilizing low-cost raw materials, such as shrimp shell by-products, and introducing energy-efficient processes such as ultrasonic pretreatment, enzymatic extraction, and microwave-assisted deacetylation. As a result of cost analysis, the biodegradable plastic of the present invention was evaluated to be approximately 30% cheaper than commercial PLA. This is an important competitive factor in the commercialization of biodegradable plastics.

[0255] In terms of environmental aspects, it incorporates numerous eco-friendly elements such as the recycling of fisheries waste, biological crosslinking, and the use of plant-based plasticizers, thereby meeting the demands of the times for the development of sustainable materials. As a result of a life cycle assessment (LCA), the biodegradable plastic of the present invention was evaluated to be able to reduce the carbon footprint by approximately 60% compared to petroleum-based plastics.

[0256] In terms of applicability, the biodegradable plastic of the present invention can be applied to various fields such as disposable products, food packaging materials, agricultural films, and medical materials. In particular, its application as a food packaging material utilizing the antibacterial properties of chitosan is promising. As a result of food preservation experiments, it was confirmed that the shelf life of fresh food packaged with the biodegradable plastic of the present invention was extended by approximately 40% compared to conventional packaging materials.

[0257] In conclusion, the biodegradable plastic utilizing shrimp shell byproducts developed in this invention is evaluated as a material suitable for actual industrial applications, as its mechanical properties, thermal stability, biodegradability, water resistance, and economic feasibility are comprehensively optimized. In particular, by optimizing the critical ranges of key variables at each process stage, the limitations of existing biodegradable plastics were overcome, and the potential as an eco-friendly material capable of replacing petroleum-based plastics was demonstrated.

[0258] 7. Conclusion

[0259] In this study, a method for manufacturing biodegradable plastics using shrimp shell byproducts was developed, and optimal conditions for key variables at each process stage were determined. Through systematic experiments using examples and comparative examples, the following key conclusions were drawn:

[0260] First, it was confirmed that pretreatment conditions of a sodium chloride concentration of 0.5-1.5 parts by weight, an ultrasonic frequency of 20-40 kHz, and a treatment time of 15-25 minutes are optimal conditions for effectively removing impurities from shrimp shell by-products while preserving the molecular structure of chitin. In particular, the process time could be reduced by approximately 50% compared to the conventional method through ultrasonic treatment.

[0261] Second, it was proven that conditions of a hydrochloric acid concentration of 1.8-2.2 parts by weight, an ethanol:acetone ratio of 3:2, and an addition amount of 2-5 parts by weight of an enzyme complex are critical conditions for optimizing the purity and yield of chitin extraction. In particular, a 1:1 ratio combination of protease and lipase was able to effectively remove proteins and lipids contained in shrimp shells, thereby maximizing chitin purity.

[0262] Third, it was confirmed that conditions of a sodium hydroxide concentration of 35-45 parts by weight, an ascorbic acid addition amount of 0.5-1.5 parts by weight, a microwave power of 600-800 W, and 6-8 processing cycles are critical conditions for optimizing the degree of deacetylation and molecular weight of chitosan. In particular, through microwave-assisted deacetylation technology, it was possible to produce high molecular weight chitosan while reducing the process time by approximately 85% compared to the conventional method.

[0263] Fourth, it was proven that the conditions of adding 0.5-1.5 parts by weight of zennipin, 0.3-0.7 parts by weight of graphene oxide, 15-25 parts by weight of epoxidized soybean oil, and 30-40 parts by weight of starch:PCL blend are critical conditions for optimizing the mechanical properties, thermal stability, processability, and biodegradability of chitosan-based biodegradable plastics. In particular, through the synergistic effect of these components, excellent properties such as a tensile strength of 35-48 MPa, an elongation of 150-210%, and a heat distortion temperature of 95-108℃ could be achieved.

[0264] Fifth, it was confirmed that molding conditions of mold temperature 130-150℃, injection pressure 8-15MPa, and cooling time 30-45 seconds, along with an appropriate post-treatment method, are critical conditions for optimizing the quality of biodegradable plastic products. In particular, moisture resistance could be significantly improved through UV surface treatment.

[0265] The biodegradable plastic utilizing shrimp shell byproducts developed in this study exhibits significantly improved physical properties compared to existing chitosan-based plastics and is evaluated as competitive even when compared to commercially available biodegradable plastics. In particular, by minimizing environmental burden while ensuring economic viability through the recycling of fisheries waste, the introduction of eco-friendly process technologies, and the use of plant-based plasticizers, this is considered a technological advancement that meets the contemporary demand for sustainable material development.

[0266] Future research directions may include process optimization for mass production, customized property control for various applications, and precise control of biodegradation rates; it is expected that this will further expand the industrial applicability of this technology.

Claims

Claim 1 A method for manufacturing biodegradable plastic using shrimp shell by-products comprises: (a) collecting shrimp shell by-products and washing them in a purified form; (b) extracting chitin from the washed shrimp shell by-products; (c) deacetylating the extracted chitin to produce chitosan; and (d) mixing a plasticizer, a filler, and a biodegradable auxiliary polymer with the chitosan. and (e) a step of manufacturing a biodegradable plastic product by molding the mixture; wherein step (a) comprises: (a1) a step of immersing the collected shrimp shell by-product in an aqueous solution in which 0.5-1.5 parts by weight of sodium chloride are dissolved in 100 parts by weight of water to remove foreign substances; (a2) a step of treating the immersed shrimp shell by-product for 15-25 minutes using an ultrasonic cleaner having a frequency of 20-40 kHz at a temperature of 45-55°C; (a3) ​​a step of treating the ultrasonically treated shrimp shell by-product for 2-3 hours at 60-70°C with an aqueous solution in which 0.8-1.2 parts by weight of sodium hydroxide are dissolved in 100 parts by weight of water to remove water-soluble proteins; (a4) a step of washing the protein-removed shrimp shell by-product with deionized water until the pH becomes 6.8-7.2 when measured with a pH meter to neutralize it. and (a5) a step of vacuum drying the neutralized shrimp shell by-product at 60-70°C for 8-12 hours so that the moisture content is 5% or less when measured by weight; wherein step (b) comprises, (b1) 1.8-2. to remove minerals contained in the washed shrimp shell by-product.(b2) a step of demineralizing the shrimp shell by-product at room temperature for 4-6 hours using a solution obtained by diluting 2 parts by weight of hydrochloric acid with 100 parts by weight of water; (b3) a step of performing enzymatic extraction for 12-18 hours at 38-42°C under conditions of pH 5.8-6.2 by adding 2-5 parts by weight of an enzyme complex containing commercially available Alcalase® protease and Novozym® lipase in a 1:1 weight ratio to 100 parts by weight of the shrimp shell by-product to the pigment-removed shrimp shell by-product; (b4) a step of obtaining a chitin precipitate by centrifuging the enzymatic extract (5000-6000 rpm, 20-30 min); and (b5) a step of washing the chitin precipitate three times with distilled water and then drying it under reduced pressure at 45-55°C for 10-14 hours using a porous silica drying agent to obtain chitin with a purity of 92% or higher when measured by FTIR analysis; comprising a method for manufacturing a biodegradable plastic using shrimp shell by-products. Claim 2 delete Claim 3 delete

Citation Information

Patent Citations

  • High-barrier biodegradable mulching film and preparation method thereof

    CN119039752A

  • Biodegradable resin composition and its molded article

    JP2000191930A

  • Biodegradable plastics molding products using sweet potato starchy

    KR1020010075905A

  • Krill-derived chitin product and method for producing the same

    KR1020210020092A